Iron-manganese polyanionic compound, preparation and application in sodium ion battery

By regulating the iron-manganese ratio and introducing an appropriate amount of metal ions, and doping lithium or magnesium ions at the sodium site, the problem of reversibility and low capacity caused by the difference in manganese ion radius and the presence of inert sodium ions during the charging and discharging process of sodium ion battery positive electrode material is solved, and the high rate performance and cycling stability of the material are achieved.

CN119725519AActive Publication Date: 2025-03-28DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202311265719.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28
Estimated Expiration
2043-09-28

AI Technical Summary

Technical Problem

The changes in the unit cell volume caused by the difference in the radius of manganese ions and the presence of inert sodium ions during the charging and discharging of existing sodium ion batteries lead to low reversibility and gram capacity of the material.

Method used

By regulating the iron-manganese ratio of phosphates, pyrophosphates or phosphate pyrophosphate composite polyanionic compounds and introducing a small amount of metal ions (such as Zn2+), the structure of the material is optimized, the inert sodium ions are activated, and the sodium site is doped with a small amount of lithium or magnesium ions to improve the reversibility and gram capacity of the material.

Benefits of technology

The material's rate performance, cycle stability and energy density are improved, and the discharge specific capacity and better capacity retention are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to a phosphate, pyrophosphate or phosphoric acid and pyrophosphoric acid composite polyanionic positive electrode material for a sodium ion battery, a preparation method and application of the positive electrode material in the sodium ion battery. The phosphate, pyrophosphate or phosphoric acid and pyrophosphoric acid composite polyanionic positive electrode has one or more than two of structures shown in a formula I-1 or I-2, a formula II-1 or II-2, a formula III-1 or III-2 and a formula IV-1 or IV-2. The synthesis process is simple, and the ionic conductivity and the electronic conductivity of the material are improved through a unit cell regulation mechanism; the prepared phosphate, pyrophosphate or phosphoric acid and pyrophosphoric acid composite polyanionic compound electrode material is high in gram volume and has good rate capability and cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of sodium ion batteries and relates to sodium ion battery electrode materials, in particular to phosphate, pyrophosphate or phosphate-pyrophosphate composite polyanion compound electrode materials, preparation methods and applications thereof in sodium ion battery electrode materials. Background Art

[0002] In recent years, with the introduction of the "dual carbon" policy and the goal of building a new power system dominated by new energy, the energy storage industry has always maintained a high level of attention as the key to regulating the volatility and indirectness of new energy and achieving grid stability. Alkali metal (Li, Na, K) ion batteries are an important component of portable large-scale fixed energy storage. Among them, lithium-ion batteries (LIBs) are widely used in electric vehicles and electronic devices due to their significant advantages such as high energy density, high electrode potential, stable cycle performance and environmental friendliness. However, in recent years, the limitation of lithium sources has led to high prices for lithium-ion battery cathode materials. Sodium-ion batteries have also received more and more attention because they have similar working principles to lithium-ion batteries and sodium sources are low in cost and abundant in resources. Therefore, it is particularly important to develop sodium-ion battery cathode materials with excellent performance.

[0003] Polyanion-type sodium ion battery cathode materials such as sodium iron (manganese) phosphate, sodium iron (manganese) pyrophosphate, and sodium iron (manganese) phosphate pyrophosphate have become the preferred cathode materials for alkali metal ion batteries due to their high abundance of raw materials, stable structure, high safety, and high redox potential. When manganese ions undergo electrochemical redox reactions, the ionic radius difference between high-valent manganese ions and divalent manganese ions is large, and the unit cell volume shrinks severely at the end of charging, resulting in greater resistance to sodium ions embedding into the cathode structure during discharge, resulting in poor reversibility of the battery's charge and discharge behavior; within the voltage range in which ester electrolytes can currently operate stably (<4.5V vs Na + / Na), manganese ions can generate Mn 2+ / Mn 3+ (3.6-3.8V vs Na + / Na) and Mn 3+ / Mn 4+ (4.1-4.3V vs Na + / Na) valence reaction process can achieve >1e- / Mn 2+ The electron transfer process can improve the material's gram capacity, but due to differences in the chemical environment, there are often some sodium ions in the structure that cannot achieve a reversible deintercalation process, and it is impossible to achieve 1e- / Mn 2+ The electrochemical reaction provides available sodium ions, and the presence of inert sodium ions leads to a low specific capacity of the material. Summary of the invention

[0004] The present invention provides a phosphate, pyrophosphate or phosphate pyrophosphate composite polyanion compound with a new structure. Firstly, by regulating the appropriate iron-manganese ratio in the high manganese structure, it is helpful to regulate the solid solution and phase change behavior during the charge and discharge process, improve the reversibility of the charge and discharge process, and reduce the polarization during the high-rate charge and discharge process. At the same time, the optimization of the iron-manganese ratio can form certain defect states in the structure, further improving the rate performance of the material; secondly, by introducing a small amount of metal ions (with an ionic radius similar to Mn) into the unit cell structure, the material can be further improved. 2+ The change of unit cell volume caused by the radius difference of manganese ions with different valence states during charge and discharge can be effectively alleviated, and the problem of cycle performance attenuation caused by manganese dissolution caused by radius difference can be reduced. At the same time, the problem of rate reduction caused by unit cell shrinkage caused by high-valent manganese ions can be reduced, and the structural reversibility during charge and discharge can be improved. Finally, partial ion doping at the alkali metal sodium site can realize the activation of inert sodium ions in the structure and promote the Mn 2+ / Mn 3+ / Mn 4+ The electrochemical reaction occurs, achieving higher gram capacity of the material.

[0005] Beneficial Effects

[0006] The invention of the above-mentioned phosphate, pyrophosphate or phosphate-pyrophosphate composite polyanion compound with a new structure can, firstly, improve the rate performance of the material and reduce the polarization during the charge and discharge process by regulating the iron-manganese ratio in the high manganese structure; secondly, it can effectively alleviate the change in the unit cell volume during the charge and discharge process of the manganese-based phosphate polyanion material, and improve the reversibility of the electrochemical redox behavior of manganese ions, thereby improving the rate performance and cycle stability of the material; finally, the addition of a small amount of metal ions at the sodium site can change the chemical environment of the inert sodium ions in the structure, stimulate the escape of the inert sodium ions, and promote the Mn 2+ / Mn 3+ / Mn 4+ The occurrence of electrochemical reactions increases the material's gram capacity, thereby improving the energy density of phosphate-based sodium-ion batteries;

[0007] The synthesis process is simple, and the ionic conductivity and electronic conductivity of the material are improved through the unit cell regulation mechanism. The prepared phosphate, pyrophosphate or phosphate-pyrophosphate composite polyanion compound electrode materials have high gram capacity and good rate performance and cycle stability. DETAILED DESCRIPTION

[0008] Example 1-Na 3.8 Li 0.1 Fe 1.25 Mn 1.65 Zn 2+ 0.05Zr 4+ 0.05 (PO4)2P2O7@C

[0009] 1) Add 350 mL of deionized water to a beaker, and then add 0.2125 mol of citric acid monohydrate, C6H 10 O8, 3.7g starch, 0.125mol iron nitrate nonahydrate Fe(NO3)3.9H2O, 0.165mol manganese nitrate Mn(NO3)2 aqueous solution (50wt%), 0.005mol zinc acetate dihydrate Zn(Ac)2.2H2O, 0.005mol zirconium nitrate Zr(NO3)4, the above raw materials are stirred until fully dissolved;

[0010] 2) Then, 0.39 mol of sodium dihydrogen phosphate dihydrate NaH2PO4.2H2O (sodium source / phosphorus source) and 0.01 mol of ammonium dihydrogen phosphate NH4H2PO4 (phosphorus source) were added to the aqueous solution, and stirring was continued until the raw materials were completely dissolved to form a precursor solution;

[0011] 3) passing the precursor solution into a spray drying device for spray drying (inlet temperature of 160° C., outlet temperature of 90° C., feed flow rate of 50 ml / min, compressed gas pressure of 0.8 KPa) to obtain a precursor powder;

[0012] 4) The precursor powder was then transferred into a high-temperature tube furnace protected by an argon atmosphere for heat treatment. The first stage heat treatment temperature was 300°C and the heat treatment time was 6 hours. The second stage heat treatment temperature was 650°C and the heat treatment time was 12 hours. The heat-treated product was subjected to Refined-XRD and ICP (main detection elements: Na / Fe / Mn / Zn / Zr / P) tests. Refined-XRD showed that the heat-treated product was consistent with the crystal structure of Na4Fe3(PO4)2P2O7 and belonged to the R3c space group. The ICP test showed that the element ratios of Na:Fe:Mn:Zn:Zr:P were 3.901:1.2497:1.6498:0.0498:0.0501:3.995, that is, Na 3.9 Fe 1.25 Mn 1.65 Zn 0.05 Zr 0.05 The (PO4)2P2O7@C material is consistent with the XRD refined structure and is recorded as sample 1#. XPS test is performed on the iron and manganese in sample 1#. The peak separation results show that the iron and manganese in sample 1# are Fe 2+ and Mn 2+ , while the carbon content of the material of the test sample 1# is 5wt%;

[0013] 5) Sample 1# was used as the active material, mixed evenly with the conductive agent acetylene black and the binder polyvinylidene fluoride in a mass ratio of 8:1:1, and an appropriate amount of solvent N-methylpyrrolidone was added to form a paste, which was applied on the aluminum current collector and cut into discs with a diameter of 14 mm after drying. The surface density of the active material was 1.1-3.2 mg / cm 2 (Here is 2.1 mg / cm 2 ), using this as the positive electrode of the battery, metallic sodium as the negative electrode, 1MNaClO4 / EC / DEC / 5wt%FEC as the electrolyte (EC / DEC V / V=1:1, the ratio of solvent EC / DEC used in the following examples is the same as here), and a glass fiber membrane as the diaphragm. The assembled battery was subjected to charge and discharge tests, and the charge and discharge cycles were performed 10 times at 0.2C / 0.2C in the voltage range of 1.5V-4.5V. The data of the discharge specific capacity of the stable cycle were recorded in Table 1. The battery was then charged to 4.5V and then cut off. The positive electrode sheet was removed from the battery in the glove box. After disassembling and cleaning with DMC for 5 times, it was evaporated in a glove box, and part of the electrode was taken for ICP test (main detection elements: Na / Fe / Mn / Zn / Zr / P). The ICP test results showed that the element ratio between Na:Fe:Mn:Zn:Zr:P elements was 0.899:1.247:1.649:0.049:0.0505:3.998, that is, when charged to 4.5V, there were 3 reversible sodium ions in the structure for deintercalation. At the same time, XPS test was performed on the iron and manganese elements in the above-mentioned electrode. The peak separation results showed that the iron and manganese in the above-mentioned electrode were Fe 3+ and Mn 3+ , that is, only Fe 2+ / 3+ and Mn 2+ / 3+ Redox reaction between

[0014] 6) The electrode evaporated in step 5) was reassembled into a half-cell with a metal lithium negative electrode in a glove box. The electrolyte was 0.2 mol / L LiPF6 + 0.8 mol / L NaClO4 / EC / DEC / 5 wt% FEC (EC / DEC V / V = ​​1:1, the ratio of solvent EC / DEC used in the following examples is the same as here), and the separator was a glass fiber membrane. At 4.3V-4.6V vs Li + The charge and discharge cycles were performed 10 times in the voltage range of 4.6 V vs Li at a rate of 0.2 C / 0.2 C. The data of the charge capacity of the first cycle and the discharge capacity of the last cycle are recorded in Table 1. + / Li is cut off, the positive electrode is disassembled from the battery in the glove box, washed with DMC for 5 times, and then evaporated to dryness in the glove box; the electrode disassembled and washed in step 6) is subjected to ICP test, and the test results show that the element ratios of Na:Li:Fe:Mn:Zn:Zr:P are 0.789:0.095:1.246:1.648:0.0495:0.0493:3.992, and the iron and manganese elements in the above-mentioned electrode are tested by XPS at the same time. The peak separation results show that the iron and manganese in the above-mentioned electrode are Fe 3+ and Mn 3+ , that is, Fe 2+ / 3+ and Mn 2+ / 3+ / 4+ Redox reaction between

[0015] 7) The electrode that was disassembled and cleaned in step 6) was evaporated and dried to form a half-cell with a metal sodium negative electrode in a glove box again. The electrolyte was 1.0 mol / L NaClO4 / EC / DEC / 5 wt% FEC (EC / DEC V / V=1:1, and the ratio of solvent EC / DEC used in the following examples is the same as here). The diaphragm was a glass fiber membrane. The charge and discharge cycle was performed in the voltage range of 1.5V-4.5V. The charge and discharge cycle was performed 10 times at 0.2C / 0.2C in the voltage range of 1.5V-4.5V and 10 times at 1.0C / 1.0C. After stabilization at 0.2C / 0.2C and 1.0C / 1.0C, the electrolyte was discharged. The data of specific electric capacity are recorded in Table 1; after the discharge of step 7), the positive electrode plate is disassembled from the battery in the glove box, washed with DMC for 3-5 times, evaporated to dryness in the glove box, and the ICP test results show that the element ratios of Na:Li:Fe:Mn:Zn:Zr:P are 3.79:0.09:1.247:1.649:0.049:0.0489:4.01. At the same time, XPS is tested, and the peak separation results show that the iron and manganese in the above-mentioned electrode are Fe 2+ and Mn 2+ The electrode in the battery charged to 4.5V was washed with DMC for 5 times, evaporated in the glove box and then tested by XPS and ICP. The XPS test results showed that the prepared electrode material contained Fe 3+ and Mn 4+ , ICP test results show that the element ratio between Na:Li:Fe:Mn:Zn:Zr:P is 0.65:0.095:1.25:1.651:0.0503:0.05:4, which means that reversible embedding and extraction of >3 sodium ions can be achieved;

[0016] 8) At the same time, the capacity retention rate of the battery after the above cycle 200 times is recorded in Table 1, and the battery is disassembled in the glove box and the diaphragm is taken out, and DMC is used to clean it 3-5 times, and then evaporated in the glove box. The mass of manganese dissolved on the diaphragm and the mass of manganese in the positive electrode structure are detected by ICP technology. The percentage is recorded in Table 1;

[0017] Example 2-Na 3.8 Li 0.1 Fe 1.25 Mn 1.695 Zn 2+ 0.005 Zr 4+ 0.05 (PO4)2P2O7@C

[0018] The process and conditions are the same as in Example 1, except that:

[0019] 1) Add 350 mL of deionized water to a beaker, and then add 0.2125 mol of citric acid monohydrate, C6H 10 O8, 3.7g starch, 0.125mol iron nitrate nine hydrate Fe(NO3)3.9H2O, 0.1695mol manganese nitrate Mn(NO3)2 aqueous solution (50wt%), 0.0005mol zinc acetate dihydrate Zn(Ac)2.2H2O, 0.005mol zirconium nitrate Zr(NO3) 4, The above raw materials are stirred until fully dissolved;

[0020] 4) Refined-XRD and ICP tests were performed on the heat-treated product to find that the element ratio of Na:Fe:Mn:Zn:Zr:P was 3.901:1.248:1.649:0.00499:0.0498:3.998, that is, Na 3.9 Fe 1.25 Mn 1.65 Zn 0.005 Zr 0.05 The (PO4)2P2O7@C material is consistent with the XRD refined structure and is recorded as sample 2#. XPS test is performed on iron and manganese in sample 2#. The peak separation results show that the iron and manganese in sample 2# are Fe 2+ and Mn 2+ , while the carbon content of the material of sample 2# was tested to be 4.7wt%;

[0021] 5) Sample 2# was used as the active material. The positive electrode was disassembled from the battery in a glove box, cleaned with DMC for 3 times, evaporated to dryness in the glove box, and part of the electrode was taken for ICP test (main detection elements: Na / Fe / Mn / Zn / Zr / P). The ICP test results showed that the element ratios of Na:Fe:Mn:Zn:Zr:P were 0.895:1.25:1.65:0.00497:0.0499:3.998;

[0022] 6) The electrode disassembled in step 6) was cleaned and then subjected to ICP testing. The test results showed that the element ratio of Na:Li:Fe:Mn:Zn:Zr:P was 0.8:0.0998:1.2498:1.65:0.00498:0.05:4;

[0023] 7) Take the battery after discharge, disassemble the positive electrode from the battery in a glove box, wash it with DMC for 5 times, evaporate it in the glove box, and perform ICP test. The element ratio of Na:Li:Fe:Mn:Zn:Zr:P is 3.797:0.1:1.2498:1.65:0.00495:0.05:3.995; take the electrode in the battery charged to 4.5V and wash it with DMC for 3-5 times. The ICP test results show that the element ratio of Na:Li:Fe:Mn:Zn:Zr:P is 0.68:0.1:1.25:1.65:0.005:0.05:4;

[0024] Example 3-Na 3.8 Li 0.1 Fe 1.25 Mn 1.51 Zn 2+ 0.19 Zr 4+ 0.05 (PO4)2P2O7@C

[0025] The process and conditions are the same as in Example 1, except that:

[0026] 1) Add 350 mL of deionized water to a beaker, and then add 0.2125 mol of citric acid monohydrate, C6H 10 O8, 3.7g starch, 0.125mol iron nitrate nonahydrate Fe(NO3)3.9H2O, 0.151mol manganese nitrate Mn(NO3)2 aqueous solution (50wt%), 0.019mol zinc acetate dihydrate Zn(Ac)2.2H2O, 0.005mol zirconium nitrate Zr(NO3)4, the above raw materials are stirred until fully dissolved;

[0027] 4) Refined-XRD and ICP tests were performed on the heat-treated product, and the element ratio of Na:Fe:Mn:Zn:Zr:P was 3.901:1.248:1.509:0.19:0.0498:3.998, that is, Na 3.9 Fe 1.25 Mn 1.51 Zn 0.19 Zr 0.05 The (PO4)2P2O7@C material is consistent with the XRD refined structure and is recorded as sample 3#. XPS test is performed on iron and manganese in sample 3#. The peak separation results show that the iron and manganese in sample 3# are Fe 2+ and Mn 2+ , while the carbon content of the material of sample 1# was tested to be 5.7wt%;

[0028] 5) Sample 3# was used as the active material. The positive electrode was disassembled from the battery in a glove box, cleaned with DMC for 4 times, evaporated to dryness in the glove box, and part of the electrode was taken for ICP test (main detection elements: Na / Fe / Mn / Zn / Zr / P). The ICP test results showed that the element ratios of Na:Fe:Mn:Zn:Zr:P were 0.895:1.25:1.51:0.19:0.0499:3.998;

[0029] 6) The electrode disassembled in step 6) was cleaned and then subjected to ICP testing. The test results showed that the element ratios of Na:Li:Fe:Mn:Zn:Zr:P were 0.799:0.0998:1.2498:1.508:0.1902:0.05:3.998;

[0030] 7) Take the battery after discharge, disassemble the positive electrode from the battery in a glove box, wash it with DMC for 3-5 times, evaporate it in the glove box, and perform ICP test. The element ratio of Na:Li:Fe:Mn:Zn:Zr:P is 3.795:0.1:1.2498:1.5101:0.19:0.0499:3.995; take the electrode in the battery charged to 4.5V and wash it with DMC for 3-5 times. The ICP test results show that the element ratio of Na:Li:Fe:Mn:Zn:Zr:P is 0.7:0.1:1.2498:1.5101:0.19:0.0499:3.99;

[0031] Example 4-Na 3.89 Li 0.1 Fe 1.25 Mn 1.695 Zn 2+ 0.05 Zr4+ 0.005 (PO4)2P2O7@C

[0032] The process and conditions are the same as in Example 1, except that:

[0033] 1) Add 350 mL of deionized water to a beaker, and then add 0.2125 mol of citric acid monohydrate, C6H 10 O8, 3.7g starch, 0.125mol iron nitrate nine hydrate Fe(NO3)3.9H2O, 0.1695mol manganese nitrate Mn(NO3)2 aqueous solution (50wt%), 0.005mol zinc acetate dihydrate Zn(Ac)2.2H2O, 0.0005mol zirconium nitrate Zr(NO3) 4, The above raw materials are stirred until fully dissolved;

[0034] 2) Then, 0.399 mol of sodium dihydrogen phosphate dihydrate NaH2PO4.2H2O (sodium source / phosphorus source) and 0.001 mol of ammonium dihydrogen phosphate NH4H2PO4 (phosphorus source) were added to the aqueous solution, and stirring was continued until the raw materials were completely dissolved to form a precursor solution;

[0035] 4) Refined-XRD and ICP tests were performed on the heat-treated product to find that the element ratio of Na:Fe:Mn:Zn:Zr:P was 3.987:1.248:1.6948:0.0498:0.00498:3.998, i.e. Na 3.99 Fe 1.25 Mn 1.695 Zn 0.05 Zr 0.005 The (PO4)2P2O7@C material is consistent with the XRD refined structure and is recorded as sample 4#. XPS test is performed on iron and manganese in sample 4#. The peak separation results show that the iron and manganese in sample 4# are Fe 2+ and Mn 2+ , while the carbon content of the material of sample 4# was tested to be 4.8wt%;

[0036] 5) Sample 4# was used as the active material. The positive electrode was disassembled from the battery in a glove box, cleaned with DMC for 3 times, evaporated to dryness in the glove box, and part of the electrode was taken for ICP test (main detection elements: Na / Fe / Mn / Zn / Zr / P). The ICP test results showed that the element ratio between Na:Fe:Mn:Zn:Zr:P was 0.99:1.2495:1.6949:0.05:0.00499:3.998;

[0037] 6) After cleaning the electrode disassembled in step 6), an ICP test was performed. The test results showed that the element ratio between Na:Li:Fe:Mn:Zn:Zr:P was 0.89:0.0998:1.2498:1.6949:0.0495:0.005:3.998;

[0038] 7) Take the battery after discharge, disassemble the positive electrode from the battery in a glove box, wash it with DMC for 5 times, evaporate it in the glove box, and perform ICP test. The element ratio of Na:Li:Fe:Mn:Zn:Zr:P is 3.8905:0.0998:1.2498:1.69448:0.05:0.00499:3.995; take the electrode in the battery charged to 4.5V and wash it with DMC for 3-5 times. The ICP test results show that the element ratio of Na:Li:Fe:Mn:Zn:Zr:P is 0.689:0.1:1.25:1.695:0.05:0.00499:3.99;

[0039] Example 5-Na 3.52 Li 0.1 Fe 1.25 Mn 1.51 Zn 2+ 0.05 Zr 4+ 0.19 (PO4)2P2O7@C

[0040] The process and conditions are the same as in Example 1, except that:

[0041] 1) Add 350 mL of deionized water to a beaker, and then add 0.2125 mol of citric acid monohydrate, C6H 10 O8, 3.7g starch, 0.125mol iron nitrate nine hydrate Fe(NO3)3.9H2O, 0.15mol manganese nitrate Mn(NO3)2 aqueous solution (50wt%), 0.005mol zinc acetate dihydrate Zn(Ac)2.2H2O, 0.019mol zirconium nitrate Zr(NO3) 4, The above raw materials are stirred until fully dissolved;

[0042] 2) Then, 0.362 mol of sodium dihydrogen phosphate dihydrate NaH2PO4.2H2O (sodium source / phosphorus source) and 0.038 mol of ammonium dihydrogen phosphate NH4H2PO4 (phosphorus source) were added to the aqueous solution, and stirring was continued until the raw materials were completely dissolved to form a precursor solution;

[0043] 4) Refined-XRD and ICP tests were performed on the heat-treated product, and the element ratio of Na:Fe:Mn:Zn:Zr:P was 3.6198:1.249:1.5101:0.0498:0.1901:3.998, that is, Na 3.62 Fe 1.25 Mn 1.51 Zn 0.05 Zr 0.19 The (PO4)2P2O7@C material is consistent with the XRD refined structure and is recorded as sample 5#. XPS test is performed on iron and manganese in sample 5#. The peak separation results show that the iron and manganese in sample 5# are Fe 2+ and Mn 2+ , while the carbon content of the material of sample 1# was tested to be 4.2wt%;

[0044] 5) Sample 5# was used as the active material. The positive electrode was disassembled from the battery in a glove box, cleaned with DMC for 5 times, evaporated to dryness in the glove box, and part of the electrode was taken for ICP test (main detection elements: Na / Fe / Mn / Zn / Zr / P). The ICP test results showed that the element ratios of Na:Fe:Mn:Zn:Zr:P were 0.62:1.2495:1.51:0.05:0.19:3.998;

[0045] 6) The electrode disassembled in step 6) was cleaned and then subjected to ICP testing. The test results showed that the element ratio of Na:Li:Fe:Mn:Zn:Zr:P was 0.52:0.0998:1.2498:1.5102:0.0495:0.005:3.998;

[0046] 7) Take the battery after discharge, disassemble the positive electrode from the battery in a glove box, wash it with DMC for 5 times, evaporate it in the glove box, and perform ICP test. The element ratio of Na:Li:Fe:Mn:Zn:Zr:P is 3.52:0.0998:1.2498:1.5101:0.05:0.19:3.995; take the electrode in the battery charged to 4.5V and wash it with DMC for 3-5 times. The ICP test results show that the element ratio of Na:Li:Fe:Mn:Zn:Zr:P is 0.38:0.1:1.25:1.51:0.05:0.19:3.99;

[0047] Example 6-Na 3.89 Li 0.01 Fe 1.25 Mn 1.65 Zn 2+ 0.05 Zr 4+0.05 (PO4)2P2O7@C

[0048] The process and conditions are the same as in Example 1, except that:

[0049] 2) Then, 0.399 mol of sodium dihydrogen phosphate dihydrate NaH2PO4.2H2O (sodium source / phosphorus source) and 0.001 mol of ammonium dihydrogen phosphate NH4H2PO4 (phosphorus source) were added to the aqueous solution, and stirring was continued until the raw materials were completely dissolved to form a precursor solution;

[0050] 4) Refined-XRD and ICP (main detection elements: Na / Fe / Mn / Zn / Zr / P) tests were performed on the heat-treated product. The element ratios of Na:Fe:Mn:Zn:Zr:P in ICP test were 3.991:1.2497:1.6498:0.0498:0.0501:3.995, which is Na 3.89 Fe 1.25 Mn 1.65 Zn 0.05 Zr 0.05 The (PO4)2P2O7@C material is consistent with the XRD refined structure and is recorded as sample 6#. XPS test is performed on iron and manganese in sample 6#. The peak separation results show that the iron and manganese in sample 6# are Fe 2+ and Mn 2 + , while the carbon content of the material of sample 6# was 4.65wt%

[0051] 5) Sample 6# is used as active material

[0052] 6) The electrode evaporated in step 5) was reassembled into a half-cell with a metal lithium negative electrode in a glove box, and the electrolyte was 0.05mol / L LiPF6+0.8mol / L NaClO4 / EC / DEC / 5wt%FEC; the electrode piece disassembled and cleaned in step 6) was subjected to ICP test, and the test results showed that the element ratio between Na:Li:Fe:Mn:Zn:Zr:P elements was 0.889:0.0099:1.2478:1.648:0.0495:0.0496:3.997;

[0053] 7) Take the battery after the discharge in step 7), disassemble the positive electrode from the battery in a glove box, wash it with DMC for 5 times, evaporate it in the glove box, and perform ICP test results. The element ratio between Na:Li:Fe:Mn:Zn:Zr:P is 3.89:0.01:1.249:1.649:0.049:0.0489:4.01; take the electrode in the battery charged to 4.5V, wash it with DMC for 3-5 times, evaporate it in the glove box, and perform XPS and ICP tests. The ICP test results show that the element ratio between Na:Li:Fe:Mn:Zn:Zr:P is 0.72:0.01:1.25:1.651:0.0501:0.05:4;

[0054] Example 7-Na 3.75 Li 0.15 Fe 1.25 Mn 1.65 Zn 2+ 0.05 Zr 4+ 0.05 (PO4)2P2O7@C

[0055] The process and conditions are the same as in Example 1, except that:

[0056] 2) Then, 0.385 mol of sodium dihydrogen phosphate dihydrate NaH2PO4.2H2O (sodium source / phosphorus source) and 0.015 mol of ammonium dihydrogen phosphate NH4H2PO4 (phosphorus source) were added to the aqueous solution, and stirring was continued until the raw materials were completely dissolved to form a precursor solution;

[0057] 4) Refined-XRD and ICP (main detection elements: Na / Fe / Mn / Zn / Zr / P) tests were performed on the heat-treated product. The element ratio of Na:Fe:Mn:Zn:Zr:P in ICP test was 3.851:1.2497:1.6498:0.0498:0.0501:3.995, which is Na 3.85 Fe 1.25 Mn 1.65 Zn 0.05 Zr 0.05 The (PO4)2P2O7@C material is consistent with the XRD refined structure and is recorded as sample 7#. XPS test is performed on iron and manganese in sample 7#. The peak separation results show that the iron and manganese in sample 7# are Fe 2+ and Mn 2 + At the same time, the carbon content of the material of sample 6# was 4.58wt%

[0058] 5) Sample 7# was used as the active substance;

[0059] 6) The electrode evaporated in step 5) is reassembled into a half-cell with a metal lithium negative electrode in a glove box, and the electrolyte is 0.3 mol / L LiPF6+0.8 mol / L NaClO4 / EC / DEC / 5% FEC; the electrode piece disassembled and cleaned in step 6) is subjected to ICP test, and the test results show that the element ratio between Na:Li:Fe:Mn:Zn:Zr:P is 0.75:0.15:1.248:1.648:0.0497:0.0498:3.996;

[0060] 7) Take the battery after the discharge in step 7), disassemble the positive electrode from the battery in a glove box, wash it with DMC for 5 times, evaporate it in the glove box, and perform ICP test results. The element ratio between Na:Li:Fe:Mn:Zn:Zr:P is 3.75:0.15:1.2489:1.649:0.049:0.0489:4.01; take the electrode in the battery charged to 4.5V, wash it with DMC for 3-5 times, evaporate it in the glove box, and perform XPS and ICP tests. The ICP test results show that the element ratio between Na:Li:Fe:Mn:Zn:Zr:P is 0.665:0.101:1.25:1.651:0.0501:0.05:4;

[0061] Example 8-Na 3.8 Li 0.1 Fe 1.35 Mn 1.55 Zn 2+ 0.05 Zr 4+ 0.05 (PO4)2P2O7@C

[0062] The process and conditions are the same as in Example 1, except that:

[0063] 1) Add 350 mL of deionized water to a beaker, and then add 0.2125 mol of citric acid monohydrate, C6H 10 O8, 3.7g starch, 0.135mol iron nitrate nine hydrate Fe(NO3)3.9H2O, 0.155mol manganese nitrate Mn(NO3)2 aqueous solution (50wt%), 0.005mol zinc acetate dihydrate Zn(Ac)2.2H2O, 0.005mol zirconium nitrate Zr(NO3) 4, The above raw materials are stirred until fully dissolved;

[0064] 4) Refined-XRD and ICP (main detection elements: Na / Fe / Mn / Zn / Zr / P) tests were performed on the heat-treated product. The element ratio of Na:Fe:Mn:Zn:Zr:P in ICP test was 3.9:1.2497:1.6498:0.0498:0.0501:3.995, which is Na 3.9 Fe 1.25 Mn 1.65 Zn 0.05 Zr 0.05 The (PO4)2P2O7@C material is consistent with the XRD refined structure and is recorded as sample 8#. XPS test is performed on the iron and manganese in sample 8#. The peak separation results show that the iron and manganese in sample 8# are Fe 2+ and Mn 2+ , while the carbon content of the material of sample 8# is 5wt%

[0065] 5) Sample 8# was used as the active material; the charge was then cut off after it reached 4.5V. The positive electrode was disassembled from the battery in a glove box, cleaned 3 times with DMC, and then evaporated in the glove box. Part of the electrode was taken for ICP (main detection elements: Na / Fe / Mn / Zn / Zr / P) test. The ICP test results showed that the element ratios of Na:Fe:Mn:Zn:Zr:P were 0.899:1.347:1.549:0.049:0.0505:3.998, that is, when charged to 4.5V, there were 3 reversible sodium ions in the structure for deintercalation. At the same time, XPS test was performed on the iron and manganese elements in the above-mentioned electrode. The peak separation results showed that the iron and manganese in the above-mentioned electrode were Fe: 3+ and Mn 3+ , that is, only Fe 2+ / 3+ and Mn 2+ / 3+ Redox reaction between

[0066] 6) The electrode after disassembly and cleaning in step 6) was subjected to ICP test. The test results showed that the element ratios of Na:Li:Fe:Mn:Zn:Zr:P were 0.798:0.095:1.346:1.548:0.0495:0.0493:3.992. At the same time, XPS test was performed on the iron and manganese elements in the above electrode. The peak separation results showed that the iron and manganese in the above electrode were Fe 3+ and Mn 3+ , that is, Fe 2+ / 3+ and Mn 2+ / 3+ / 4+ Redox reaction between

[0067] 7) Take the battery after the discharge in step 7), disassemble the positive electrode from the battery in a glove box, wash it with DMC for 5 times, evaporate it in the glove box, and perform ICP test results. The element ratio between Na:Li:Fe:Mn:Zn:Zr:P is 3.79:0.099:1.347:1.549:0.0499:0.0499:4.01. At the same time, XPS is tested. The peak separation results show that the iron and manganese in the above-mentioned electrode are Fe 2+ and Mn 2+ The electrode in the battery charged to 4.5V was washed with DMC for 3-5 times, evaporated in the glove box and then tested by XPS and ICP. The XPS test results showed that the prepared electrode material contained Fe 3+ and Mn 4+ , ICP test results show that the element ratios of Na:Li:Fe:Mn:Zn:Zr:P are 0.73:0.099:1.35:1.551:0.0501:0.05:4;

[0068] Example 9-Na 3.8 Li 0.1 Fe 0.6 Mn 2.3 Zn 2+ 0.05 Zr 4+ 0.05 (PO4)2P2O7@C

[0069] The process and conditions are the same as in Example 1, except that:

[0070] 1) Add 350 mL of deionized water to a beaker, and then add 0.2125 mol of citric acid monohydrate, C6H 10 O8, 3.7g starch, 0.06mol iron nitrate nine hydrate Fe(NO3)3.9H2O, 0.23mol manganese nitrate Mn(NO3)2 aqueous solution (50wt%), 0.005mol zinc acetate dihydrate Zn(Ac)2.2H2O, 0.005mol zirconium nitrate Zr(NO3) 4, The above raw materials are stirred until fully dissolved;

[0071] 4) Refined-XRD and ICP (main detection elements: Na / Fe / Mn / Zn / Zr / P) tests were performed on the heat-treated product. The element ratio of Na:Fe:Mn:Zn:Zr:P in ICP test was 3.901:0.597:2.298:0.0498:0.0501:3.99, which is Na 3.9 Fe 0.6 Mn 2.3 Zn 0.05Zr 0.05 The (PO4)2P2O7@C material is consistent with the XRD refined structure and is recorded as sample 9#. XPS test is performed on the iron and manganese in sample 9#. The peak separation results show that the iron and manganese in sample 9# are Fe 2+ and Mn 2+ , while the carbon content of the material of sample 8# is 5wt%

[0072] 5) Sample 9# was used as the active material; the charge was then cut off after it reached 4.5V. The positive electrode was disassembled from the battery in a glove box, cleaned 3 times with DMC, and then evaporated in the glove box. Part of the electrode was taken for ICP (main detection elements: Na / Fe / Mn / Zn / Zr / P) test. The ICP test results showed that the element ratios of Na:Fe:Mn:Zn:Zr:P were 0.901:0.597:2.298:0.0498:0.0501:3.99, that is, when charged to 4.5V, there were 3 reversible sodium ions in the structure for deintercalation. At the same time, XPS test was performed on the iron and manganese elements in the above-mentioned electrode. The peak separation results showed that the iron and manganese in the above-mentioned electrode were Fe: 3+ and Mn 3+ , that is, only Fe 2+ / 3+ and Mn 2+ / 3+ Redox reaction between

[0073] 6) The electrode after disassembly and cleaning in step 6) was subjected to ICP test. The test results showed that the element ratio between Na:Li:Fe:Mn:Zn:Zr:P was 3.801:0.1:0.597:2.298:0.0498:0.0501:3.99. At the same time, XPS test was performed on the iron and manganese elements in the above electrode. The peak separation results showed that the iron and manganese in the above electrode were Fe 3+ and Mn 3+ , that is, Fe 2+ / 3+ and Mn 2+ / 3+ / 4+ Redox reaction between

[0074] 7) Take the battery after the discharge in step 7), disassemble the positive electrode from the battery in a glove box, wash it with DMC for 5 times, evaporate it in the glove box, and perform ICP test results. The element ratio between Na:Li:Fe:Mn:Zn:Zr:P is 3.81:0.1:0.597:2.298:0.0498:0.0501:3.99. At the same time, XPS is tested. The peak separation results show that the iron and manganese in the above-mentioned electrode are Fe 2+ and Mn 2+ The electrode in the battery charged to 4.5V was washed with DMC for 3-5 times, evaporated in the glove box and then tested by XPS and ICP. The XPS test results showed that the prepared electrode material contained Fe3+ and Mn 4+ , ICP test results show that the element ratio between Na:Li:Fe:Mn:Zn:Zr:P is 0.68:0.1:0.597:2.298:0.0498:0.0501:3.99;

[0075] Example 10-Na 3.8 Mg 0.05 Fe 1.25 Mn 1.65 Zn 2+ 0.05 Zr 4+ 0.05 (PO4)2P2O7@C

[0076] The process and conditions are the same as in Example 1, except that:

[0077] 4) Recorded as sample 10#, the iron and manganese ions in sample 10# were tested by XPS. The peak separation results showed that the iron and manganese in sample 10# were Fe 2+ and Mn 2+ , while the carbon content of the material of sample 10# is 4.25wt%

[0078] 5) Sample 10# is used as the active substance,

[0079] 6) The electrode evaporated in step 5) was reassembled into a half-cell with a metal lithium negative electrode in a glove box, the electrolyte was 0.2 mol / L Mg(TFSI)2+0.8 mol / L NaClO4 / EC / DEC / 5% FEC, and the diaphragm was a glass fiber membrane. The electrode was heated to 4.0 V-4.2 V vs Mg 2+ / Mg voltage range, the charge and discharge cycle was performed 10 times at a rate of 0.2C / 0.2C, and the data of the charge capacity of the first cycle and the discharge capacity of the last cycle were recorded in Table 1. After charging to 4.2V vs Mg 2+ / Mg, the positive electrode sheet was disassembled from the battery in a glove box, washed with DMC for 3-5 times, and then evaporated to dryness in the glove box; the electrode sheet disassembled and washed in step 6) was subjected to ICP test, and the test results showed that the element ratio between Na:Mg:Fe:Mn:Zn:Zr:P was 0.799:0.0495:1.246:1.648:0.0498:0.0497:3.997;

[0080] 7) Take the battery after the discharge in step 7), disassemble the positive electrode from the battery in a glove box, wash it with DMC three times, evaporate it in the glove box, and perform ICP test results. The element ratio between Na:Mg:Fe:Mn:Zn:Zr:P is 3.79:0.049:1.247:1.649:0.049:0.0489:4.01. At the same time, XPS is tested. The peak separation results show that the iron and manganese in the above-mentioned electrode are Fe 2+ and Mn 2+ The electrode in the battery charged to 4.5V was washed with DMC for 5 times, evaporated in the glove box and then tested by XPS and ICP. The XPS test results showed that the prepared electrode material contained Fe 3+ and Mn 4+ The ICP test results show that the element ratio between Na:Mg:Fe:Mn:Zn:Zr:P is 0.68:0.0495:1.25:1.6501:0.0501:0.05:4.

[0081] Comparative Example 1-Na 3.8 Li 0.1 Fe 1.25 Mn 1.699 Zn 2+ 0.001 Zr 4+ 0.05 (PO4)2P2O7@C

[0082] 1) Add 350 mL of deionized water to a beaker, and then add 0.2125 mol of citric acid monohydrate, C6H 10 O8, 3.7g starch, 0.125mol iron nitrate nine hydrate Fe(NO3)3.9H2O, 0.1699mol manganese nitrate Mn(NO3)2 aqueous solution (50wt%), 0.0001mol zinc acetate dihydrate Zn(Ac)2.2H2O, 0.005mol zirconium nitrate Zr(NO3) 4, The above raw materials are stirred until fully dissolved;

[0083] 2) Then, 0.39 mol of sodium dihydrogen phosphate dihydrate NaH2PO4.2H2O (sodium source / phosphorus source) and 0.01 mol of ammonium dihydrogen phosphate NH4H2PO4 (phosphorus source) were added to the aqueous solution, and stirring was continued until the raw materials were completely dissolved to form a precursor solution;

[0084] 3) passing the precursor solution into a spray drying device for spray drying (inlet temperature of 160° C., outlet temperature of 90° C., feed flow rate of 50 ml / min, compressed gas pressure of 0.8 KPa) to obtain a precursor powder;

[0085] 4) The precursor powder was then transferred into a high-temperature tube furnace protected by an argon atmosphere for heat treatment. The first stage heat treatment temperature was 300°C and the heat treatment time was 6 hours. The second stage heat treatment temperature was 650°C and the heat treatment time was 12 hours. The heat-treated product was subjected to Refined-XRD and ICP (main detection elements: Na / Fe / Mn / Zn / Zr / P) tests. Refined-XRD showed that the heat-treated product was consistent with the crystal structure of Na4Fe3(PO4)2P2O7 and belonged to the R3c space group. The ICP test showed that the element ratio between Na:Fe:Mn:Zn:Zr:P was 3.90:1.2497:1.699:0.001:0.0501:3.995, that is, Na 3.9 Fe 1.25 Mn 1.699 Zn 0.001 Zr 0.05 The (PO4)2P2O7@C material is consistent with the XRD refined structure and is recorded as sample A#. XPS test is performed on the iron and manganese in sample A#. The peak separation results show that the iron and manganese in sample A# are Fe 2+ and Mn 2+ , while the carbon content of the material of the test sample A# is 5wt%;

[0086] 5) Sample A# was used as the active material, mixed evenly with the conductive agent acetylene black and the binder polyvinylidene fluoride in a mass ratio of 8:1:1, and an appropriate amount of solvent N-methylpyrrolidone was added to form a paste, which was applied on the aluminum current collector and dried and cut into discs with a diameter of 14 mm. The surface density of the active material was 1.1-3.2 mg / cm 2 (Here is 2.1 mg / cm 2), using this as the positive electrode of the battery, metallic sodium as the negative electrode, 1MNaClO4 / EC / DEC / 5wt%FEC (EC / DEC V / V=1:1) as the electrolyte, and a glass fiber membrane as the separator. The assembled battery was subjected to charge and discharge tests, and the charge and discharge cycles were performed 10 times under 0.2C / 0.2C conditions in the voltage range of 1.5V-4.5V. The data of the discharge specific capacity of the stable cycle were recorded in Table 1. The battery was then charged to 4.5V and then cut off. The positive electrode sheet was disassembled from the battery in the glove box and cleaned with DMC. After 3-5 times, evaporate to dryness in a glove box, take part of the electrode for ICP test (main detection elements: Na / Fe / Mn / Zn / Zr / P). The ICP test results show that the element ratio between Na:Fe:Mn:Zn:Zr:P is 0.899:1.247:1.699:0.001:0.0502:3.998, that is, when charged to 4.5V, there are 3 reversible sodium ions in the structure for deintercalation. At the same time, XPS test is performed on the iron and manganese elements in the above-mentioned electrode. The peak separation results show that the iron and manganese in the above-mentioned electrode are Fe 3+ and Mn 3+ , that is, only Fe 2+ / 3+ and Mn 2+ / 3+ Redox reaction between

[0087] 6) The electrode evaporated in step 5) was reassembled into a half-cell with a metal lithium negative electrode in a glove box, the electrolyte was 0.2 mol / L LiPF6+0.8 mol / L NaClO4 / EC / DEC / 5 wt% FEC, and the separator was a glass fiber membrane. + The charge and discharge cycles were performed 10 times in the voltage range of 4.6 V vs Li at a rate of 0.2 C / 0.2 C. The data of the charge capacity of the first cycle and the discharge capacity of the last cycle are recorded in Table 1. + / Li is cut off, the positive electrode plate is disassembled from the battery in the glove box, washed with DMC for 3-5 times, and then evaporated to dryness in the glove box; the electrode plate disassembled and washed in step 6) is subjected to ICP test, and the test results show that the element ratio between Na:Li:Fe:Mn:Zn:Zr:P is 0.799:0.01:1.246:1.699:0.001:0.0493:3.992, and the iron and manganese elements in the above-mentioned electrode plate are tested by XPS at the same time. The peak separation results show that the iron and manganese in the above-mentioned electrode plate are Fe 3+ and Mn 3+ , that is, Fe 2+ / 3+ and Mn 2+ / 3+ / 4+ Redox reaction between

[0088] 7) The electrode disassembled and cleaned in step 6) was evaporated and dried to form a half-cell with a metal sodium negative electrode in a glove box again. The electrolyte was 1.0 mol / L NaClO4 / EC / DEC / 5% FEC, and a glass fiber membrane was used as a separator. The charge and discharge cycle was performed in the voltage range of 1.5V-4.5V, and the charge and discharge cycle was performed 10 times at 0.2C / 0.2C in the voltage range of 1.5V-4.5V and 10 times at 1.0C / 1.0C. The data of the discharge specific capacity after stabilization at 0.2C / 0.2C and 1.0C / 1.0C were recorded in Table 1; the discharge in step 7) was performed After the battery is finished, the positive electrode is disassembled from the battery in the glove box, washed with DMC for 3-5 times, and then evaporated in the glove box. The ICP test results show that the element ratios of Na:Li:Fe:Mn:Zn:Zr:P are 3.8:0.1:1.247:1.699:0.001:0.0499:4.01. At the same time, XPS is tested. The peak separation results show that the iron and manganese in the above-mentioned electrode are Fe 2+ and Mn 2+ The electrode in the battery charged to 4.5V was washed with DMC for 3-5 times, evaporated in the glove box and then tested by XPS and ICP. The XPS test results showed that the prepared electrode material contained Fe 3+ and Mn 4 + , ICP test results show that the element ratio between Na:Li:Fe:Mn:Zn:Zr:P is 0.75:0.1:1.25:1.699:0.001:0.05:4;

[0089] 8) At the same time, the capacity retention rate of the battery after the above cycle 200 times is recorded in Table 1, and the battery is disassembled in the glove box and the diaphragm is taken out, and DMC is used to clean it 3-5 times, and then evaporated in the glove box. The mass of manganese dissolved on the diaphragm and the mass of manganese in the positive electrode structure are detected by ICP technology. The percentage is recorded in Table 1;

[0090] Comparative Example 2-Na 3.8 Li 0.1 Fe 1.075 Mn 1.42 Zn 2+ 0.5 Zr 4+ 0.05 (PO4)2P2O7@C

[0091] The process and conditions are the same as those of Comparative Example 1, except that:

[0092] 1) Add 350 mL of deionized water to a beaker, and then add 0.2125 mol of citric acid monohydrate, C6H 10O8, 3.7g starch, 0.01075mol iron nitrate nonahydrate Fe(NO3)3.9H2O, 0.142mol manganese nitrate Mn(NO3)2 aqueous solution (50wt%), 0.05mol zinc acetate dihydrate Zn(Ac)2.2H2O, 0.005mol zirconium nitrate Zr(NO3)4, the above raw materials are stirred until fully dissolved;

[0093] 4) Refined-XRD and ICP (main detection elements: Na / Fe / Mn / Zn / Zr / P) tests were performed on the heat-treated product. The element ratio of Na:Fe:Mn:Zn:Zr:P in ICP test was 3.90:1.075:1.42:0.5:0.05:3.997, which is Na 3.9 Fe 1.075 Mn 1.42 Zn 0.5 Zr 0.05 The (PO4)2P2O7@C material is consistent with the XRD refined structure and is recorded as sample A#. XPS test is performed on the iron and manganese in sample A#. The peak separation results show that the iron and manganese in sample A# are Fe 2+ and Mn 2+ , while the carbon content of the material of the test sample A# is 5wt%;

[0094] 5) Sample A# was used as the active material and charged to 4.5V before being cut off. The positive electrode was disassembled from the battery in a glove box, cleaned with DMC for 3-5 times, and then evaporated to dryness in the glove box. Part of the electrode was taken for ICP test (main detection elements: Na / Fe / Mn / Zn / Zr / P). The ICP test results showed that the element ratios of Na:Fe:Mn:Zn:Zr:P were 0.899:1.075:1.42:0.5:0.05:3.998, that is, when charged to 4.5V, there were 3 reversible sodium ions in the structure for deintercalation. At the same time, XPS test was performed on the iron and manganese elements in the above-mentioned electrode. The peak separation results showed that the iron and manganese in the above-mentioned electrode were Fe: 3+ and Mn 3 + , that is, only Fe 2+ / 3+ and Mn 2+ / 3+ Redox reaction between

[0095] 6) The electrode after disassembly and cleaning in step 6) was subjected to ICP test. The test results showed that the element ratio between Na:Li:Fe:Mn:Zn:Zr:P was 0.799:0.1:1.075:1.42:0.5:0.05:3.992. At the same time, XPS test was performed on the iron and manganese elements in the above electrode. The peak separation results showed that the iron and manganese in the above electrode were Fe 3+ and Mn3+ , that is, Fe 2+ / 3+ and Mn 2+ / 3+ / 4+ Redox reaction between

[0096] 7) Take the battery after the discharge in step 7), disassemble the positive electrode from the battery in a glove box, wash it with DMC for 3-5 times, evaporate it in the glove box, and perform ICP test results. The element ratio between Na:Li:Fe:Mn:Zn:Zr:P is 3.8:0.1:1.075:1.42:0.5:0.05:4.01. At the same time, XPS is tested. The peak separation results show that the iron and manganese in the above-mentioned electrode are Fe 2+ and Mn 2+ The electrode in the battery charged to 4.5V was washed with DMC for 3-5 times, evaporated in the glove box and then tested by XPS and ICP. The XPS test results showed that the prepared electrode material contained Fe 3+ and Mn 4+ , ICP test results show that the element ratio between Na:Li:Fe:Mn:Zn:Zr:P is 0.72:0.1:1.075:1.42:0.5:0.05:4;

[0097] Comparative Example 3-Na 3.794 Li 0.1 Fe 1.25 Mn 1.697 Zn 2+ 0.05 Zr 4+ 0.003 (PO4)2P2O7@C

[0098] The process and conditions are the same as those of Comparative Example 1, except that:

[0099] 1) Add 350 mL of deionized water to a beaker, and then add 0.2125 mol of citric acid monohydrate, C6H 10 O8, 3.7g starch, 0.125mol iron nitrate nine hydrate Fe(NO3)3.9H2O, 0.1697mol manganese nitrate Mn(NO3)2 aqueous solution (50wt%), 0.005mol zinc acetate dihydrate Zn(Ac)2.2H2O, 0.0003mol zirconium nitrate Zr(NO3) 4, The above raw materials are stirred until fully dissolved;

[0100] 2) Then, 0.3894 mol of sodium dihydrogen phosphate dihydrate NaH2PO4.2H2O (sodium source / phosphorus source) and 0.0106 mol of ammonium dihydrogen phosphate NH4H2PO4 (phosphorus source) were added to the aqueous solution, and stirring was continued until the raw materials were completely dissolved to form a precursor solution;

[0101] 4) Refined-XRD and ICP (main detection elements: Na / Fe / Mn / Zn / Zr / P) tests were performed on the heat-treated product. The element ratios of Na:Fe:Mn:Zn:Zr:P in ICP test were 3.894:1.2497:1.697:0.0499:0.00299:3.99, which is Na 3.894 Fe 1.25 Mn 1.697 Zn 0.05 Zr 0.003 The (PO4)2P2O7@C material is consistent with the XRD refined structure and is recorded as sample C#. XPS test is performed on iron and manganese in sample A#. The peak separation results show that the iron and manganese in sample C# are Fe 2+ and Mn 2 + , while the carbon content of the material of the test sample C# is 4.8wt%

[0102] 5) Sample C# was used as the active material; the battery was charged to 4.5V and then cut off. The positive electrode was disassembled from the battery in a glove box, cleaned with DMC for 3-5 times, evaporated to dryness in the glove box, and part of the electrode was taken for ICP test (main detection elements: Na / Fe / Mn / Zn / Zr / P). The ICP test results showed that the element ratios of Na:Fe:Mn:Zn:Zr:P were 0.894:1.2497:1.697:0.0498:0.00299:3.998;

[0103] 6) The electrode after disassembly and cleaning in step 6) was subjected to ICP test. The test results showed that the element ratios of Na:Li:Fe:Mn:Zn:Zr:P were 0.794:0.1:1.2496:1.697:0.04995:0.00299:3.997. At the same time, XPS test was performed on the iron and manganese elements in the above electrode. The peak separation results showed that the iron and manganese in the above electrode were Fe 3+ and Mn 3+ , that is, Fe 2+ / 3+ and Mn 2+ / 3+ / 4+ Redox reaction between

[0104] 7) The ICP test results show that the element ratios of Na:Li:Fe:Mn:Zn:Zr:P are 3.794:0.1:1.2497:1.697:0.04998:0.00299:4.01. XPS is also performed to test the peaks. The iron and manganese in the above-mentioned electrode are Fe 2+ and Mn 2+The electrode in the battery charged to 4.5V was washed with DMC for 3-5 times, evaporated in the glove box and then tested by XPS and ICP. The XPS test results showed that the prepared electrode material contained Fe 3+ and Mn 4+ , ICP test results show that the element ratio between Na:Li:Fe:Mn:Zn:Zr:P is 0.71:0.1:1.2497:1.697:0.04998:0.00299:4.01;

[0105] Comparative Example 4-Na 3.2 Li 0.1 Fe 1.17 Mn 1.48 Zn 2+ 0.05 Zr 4+ 0.3 (PO4)2P2O7@C

[0106] The process and conditions are the same as those of Comparative Example 1, except that:

[0107] 1) Add 350 mL of deionized water to a beaker, and then add 0.2125 mol of citric acid monohydrate, C6H 10 O8, 3.7g starch, 0.117mol iron nitrate nine hydrate Fe(NO3)3.9H2O, 0.148mol manganese nitrate Mn(NO3)2 aqueous solution (50wt%), 0.005mol zinc acetate dihydrate Zn(Ac)2.2H2O, 0.03mol zirconium nitrate Zr(NO3) 4, The above raw materials are stirred until fully dissolved;

[0108] 2) Then, 0.32 mol of sodium dihydrogen phosphate dihydrate NaH2PO4.2H2O (sodium source / phosphorus source) and 0.08 mol of ammonium dihydrogen phosphate NH4H2PO4 (phosphorus source) were added to the aqueous solution, and stirring was continued until the raw materials were completely dissolved to form a precursor solution;

[0109] 4) Refined-XRD and ICP (main detection elements: Na / Fe / Mn / Zn / Zr / P) tests were performed on the heat-treated product. The element ratio of Na:Fe:Mn:Zn:Zr:P in ICP test was 3.3:1.17:1.48:0.05:0.3:3.99, which is Na 3.3 Fe 1.17 Mn 1.48 Zn 0.05 Zr 0.3The (PO4)2P2O7@C material is consistent with the XRD refined structure and is recorded as sample D#. XPS test is performed on the iron and manganese in sample D#. The peak separation results show that the iron and manganese in sample C# are Fe 2+ and Mn 2+ , while the carbon content of the material of the test sample D# was 4.6wt%;

[0110] 5) Sample D# was used as the active material; the battery was charged to 4.5V and then cut off. The positive electrode was disassembled from the battery in a glove box, cleaned with DMC for 3-5 times, evaporated to dryness in the glove box, and part of the electrode was taken for ICP test (main detection elements: Na / Fe / Mn / Zn / Zr / P). The ICP test results showed that the element ratios of Na:Fe:Mn:Zn:Zr:P were 0.3:1.17:1.48:0.05:0.3:3.998;

[0111] 6) The electrode after disassembly and cleaning in step 6) was subjected to ICP test. The test results showed that the element ratio between Na:Li:Fe:Mn:Zn:Zr:P was 0.2:0.1:1.17:1.48:0.05:0.3:3.997. At the same time, XPS test was performed on the iron and manganese elements in the above electrode. The peak separation results showed that the iron and manganese in the above electrode were Fe 3+ and Mn 3+ , that is, Fe 2+ / 3+ and Mn 2 + / 3+ / 4+ Redox reaction between

[0112] 7) The ICP test results show that the element ratios of Na:Li:Fe:Mn:Zn:Zr:P are 3.2:0.1:1.17:1.48:0.05:0.3:4.01. XPS is also performed to test the peaks. The iron and manganese in the above-mentioned electrode are Fe 2+ and Mn 2 + The electrode in the battery charged to 4.5V was washed with DMC for 3-5 times, evaporated in the glove box and then tested by XPS and ICP. The XPS test results showed that the prepared electrode material contained Fe 3+ and Mn 4+ , ICP test results show that the element ratio between Na:Li:Fe:Mn:Zn:Zr:P is 0.2:0.1:1.17:1.48:0.05:0.4:4.01;

[0113] Comparative Example 5-Na 3.795 Li 0.005 Fe 1.25 Mn 1.65 Zn2+ 0.05 Zr 4+ 0.05 (PO4)2P2O7@C

[0114] The process and conditions are the same as those of Comparative Example 1, except that:

[0115] 1) Add 350 mL of deionized water to a beaker, and then add 0.2125 mol of citric acid monohydrate, C6H 10 O8, 3.7g starch, 0.125mol iron nitrate nine hydrate Fe(NO3)3.9H2O, 0.165mol manganese nitrate Mn(NO3)2 aqueous solution (50wt%), 0.005mol zinc acetate dihydrate Zn(Ac)2.2H2O, 0.005mol zirconium nitrate Zr(NO3) 4, The above raw materials are stirred until fully dissolved;

[0116] 2) Then, 0.3895 mol of sodium dihydrogen phosphate dihydrate NaH2PO4.2H2O (sodium source / phosphorus source) and 0.0105 mol of ammonium dihydrogen phosphate NH4H2PO4 (phosphorus source) were added to the aqueous solution, and stirring was continued until the raw materials were completely dissolved to form a precursor solution;

[0117] 4) Refined-XRD and ICP (main detection elements: Na / Fe / Mn / Zn / Zr / P) tests were performed on the heat-treated product. The element ratio of Na:Fe:Mn:Zn:Zr:P in ICP test was 3.895:1.2497:1.648:0.05:0.0501:3.999, which is Na 3.895 Fe 1.25 Mn 1.65 Zn 0.05 Zr 0.05 The (PO4)2P2O7@C material is consistent with the XRD refined structure and is recorded as sample E#. XPS test is performed on the iron and manganese in sample E#. The peak separation results show that the iron and manganese in sample E# are Fe 2+ and Mn 2 + , while the carbon content of the material of the test sample E# is 5wt%;

[0118] 5) Sample E# was used as the active material; the charge was then cut off after being charged to 4.5V. The positive electrode was disassembled from the battery in a glove box, cleaned with DMC for 3-5 times, evaporated to dryness in the glove box, and part of the electrode was tested by ICP (main detection elements: Na / Fe / Mn / Zn / Zr / P). The ICP test results showed that the element ratios of Na:Fe:Mn:Zn:Zr:P were 0.895:1.2497:1.649:0.0498:0.0501:3.998, that is, when charged to 4.5V, there were 3 reversible sodium ions in the structure for deintercalation. At the same time, XPS tests were performed on the iron and manganese elements in the above-mentioned electrode. The peak separation results showed that the iron and manganese in the above-mentioned electrode were Fe: 3+ and Mn 3+ , that is, only Fe 2+ / 3+ and Mn 2+ / 3+ Redox reaction between

[0119] 6) The electrode evaporated in step 5) was reassembled into a half-cell with a metal lithium negative electrode in a glove box, and the electrolyte was 0.01 mol / L LiPF6 + 0.8 mol / L NaClO4 / EC / DEC / 5% FEC; then charged to 4.6 V vs Li + / Li is cut off, the positive electrode is disassembled from the battery in the glove box, washed with DMC for 3-5 times, and then evaporated to dryness in the glove box; the electrode disassembled and washed in step 6) is subjected to ICP test, and the test results show that the element ratio between Na:Li:Fe:Mn:Zn:Zr:P is 0.795:0.005:1.248:1.6498:0.04995:0.0498:3.992, and the iron and manganese elements in the above-mentioned electrode are tested by XPS at the same time. The peak separation results show that the iron and manganese in the above-mentioned electrode are Fe 3+ and Mn 3+ , that is, Fe 2+ / 3+ and Mn 2 + / 3+ / 4+ Redox reaction between

[0120] 7) Take the battery after the discharge in step 7), disassemble the positive electrode from the battery in a glove box, wash it with DMC for 3-5 times, evaporate it in the glove box, and perform ICP test results. The element ratio between Na:Li:Fe:Mn:Zn:Zr:P is 3.895:0.005:1.249:1.6499:0.04996:0.0499:4.01. At the same time, XPS is tested. The peak separation results show that the iron and manganese in the above-mentioned electrode are Fe 2+ and Mn 2+The electrode in the battery charged to 4.5V was washed with DMC for 3-5 times, evaporated in the glove box and then tested by XPS and ICP. The XPS test results showed that the prepared electrode material contained Fe 3+ and Mn 4+ , ICP test results show that the element ratio between Na:Li:Fe:Mn:Zn:Zr:P is 0.83:0.005:1.25:1.64995:0.0495:0.05:4;

[0121] Comparative Example 6-Na 3.7 Li 0.2 Fe 1.25 Mn 1.65 Zn 2+ 0.05 Zr 4+ 0.05 (PO4)2P2O7@C

[0122] The process and conditions are the same as those of Comparative Example 1, except that:

[0123] 1) Add 350 mL of deionized water to a beaker, and then add 0.2125 mol of citric acid monohydrate, C6H 10 O8, 3.7g starch, 0.125mol iron nitrate nine hydrate Fe(NO3)3.9H2O, 0.165mol manganese nitrate Mn(NO3)2 aqueous solution (50wt%), 0.005mol zinc acetate dihydrate Zn(Ac)2.2H2O, 0.005mol zirconium nitrate Zr(NO3) 4, The above raw materials are stirred until fully dissolved;

[0124] 2) Then, 0.39 mol of sodium dihydrogen phosphate dihydrate NaH2PO4.2H2O (sodium source / phosphorus source) and 0.01 mol of ammonium dihydrogen phosphate NH4H2PO4 (phosphorus source) were added to the aqueous solution, and stirring was continued until the raw materials were completely dissolved to form a precursor solution;

[0125] 4) Refined-XRD and ICP (main detection elements: Na / Fe / Mn / Zn / Zr / P) tests were performed on the heat-treated product. The element ratio of Na:Fe:Mn:Zn:Zr:P in ICP test was 3.8:1.2497:1.648:0.05:0.0501:3.999, which is Na 3.8 Fe 1.25 Mn 1.65 Zn 0.05 Zr 0.05The (PO4)2P2O7@C material is consistent with the XRD refined structure and is recorded as sample F#. XPS test is performed on the iron and manganese in sample F#. The peak separation results show that the iron and manganese in sample E# are Fe 2+ and Mn 2+ , while the carbon content of the material of the test sample E# is 5wt%;

[0126] 5) Sample F# was used as the active material; the charge was then cut off after being charged to 4.5V. The positive electrode was disassembled from the battery in a glove box, cleaned with DMC for 3-5 times, evaporated to dryness in the glove box, and part of the electrode was taken for ICP (main detection elements: Na / Fe / Mn / Zn / Zr / P) test. The ICP test results showed that the element ratios of Na:Fe:Mn:Zn:Zr:P were 0.8:1.247:1.649:0.0498:0.0501:3.998, that is, when charged to 4.5V, there were 3 reversible sodium ions in the structure for deintercalation. At the same time, XPS test was performed on the iron and manganese elements in the above-mentioned electrode. The peak separation results showed that the iron and manganese in the above-mentioned electrode were Fe:Mn:Zn:Zr:P, respectively. 3+ and Mn 3+ , that is, only Fe 2+ / 3+ and Mn 2+ / 3+ Redox reaction between

[0127] 6) The electrode evaporated in step 5) was reassembled into a half-cell with a metal lithium negative electrode in a glove box, and the electrolyte was 0.5 mol / L LiPF6 + 0.8 mol / L NaClO4 / EC / DEC / 5% FEC; then charged to 4.6 V vs Li + / Li is cut off, the positive electrode plate is disassembled from the battery in the glove box, washed with DMC for 3-5 times, and then evaporated to dryness in the glove box; the electrode plate disassembled and washed in step 6) is subjected to ICP test, and the test results show that the element ratio between Na:Li:Fe:Mn:Zn:Zr:P is 0.7:0.2:1.248:1.6498:0.04995:0.0498:3.992, and the iron and manganese elements in the above-mentioned electrode plate are tested by XPS at the same time. The peak separation results show that the iron and manganese in the above-mentioned electrode plate are Fe 3+ and Mn 3+ , that is, Fe 2+ / 3+ and Mn 2+ / 3+ / 4+ Redox reaction between

[0128] 7) Take the battery after the discharge in step 7), disassemble the positive electrode from the battery in a glove box, wash it with DMC for 3-5 times, evaporate it in the glove box, and perform ICP test results. The element ratio between Na:Li:Fe:Mn:Zn:Zr:P is 3.7:0.2:1.249:1.6499:0.04996:0.0499:4.01. At the same time, XPS is tested. The peak separation results show that the iron and manganese in the above-mentioned electrode are Fe 2+ and Mn 2+ The electrode in the battery charged to 4.5V was washed with DMC for 3-5 times, evaporated in the glove box and then tested by XPS and ICP. The XPS test results showed that the prepared electrode material contained Fe 3+ and Mn 4+ , ICP test results show that the element ratio between Na:Li:Fe:Mn:Zn:Zr:P is 0.7:0.2:1.25:1.64995:0.0495:0.05:4;

[0129] Comparative Example 7-Na 3.8 Li 0.1 Fe 1.45 Mn 1.45 Zn 2+ 0.05 Zr 4+ 0.05 (PO4)2P2O7@C

[0130] The process and conditions are the same as those of Comparative Example 1, except that:

[0131] 1) Add 350 mL of deionized water to a beaker, and then add 0.2125 mol of citric acid monohydrate, C6H 10 O8, 3.7g starch, 0.145mol iron nitrate nine hydrate Fe(NO3)3.9H2O, 0.145mol manganese nitrate Mn(NO3)2 aqueous solution (50wt%), 0.005mol zinc acetate dihydrate Zn(Ac)2.2H2O, 0.005mol zirconium nitrate Zr(NO3) 4, The above raw materials are stirred until fully dissolved;

[0132] 4) Refined-XRD and ICP (main detection elements: Na / Fe / Mn / Zn / Zr / P) tests were performed on the heat-treated product. The element ratio of Na:Fe:Mn:Zn:Zr:P in ICP test was 3.9:1.2497:1.648:0.05:0.0501:3.999, which is Na 3.9 Fe 1.45 Mn 1.45 Zn2+ 0.05 Zr 4+ 0.05 The (PO4)2P2O7@C material is consistent with the XRD refined structure and is recorded as sample G#. XPS test is performed on the iron and manganese in sample G#. The peak separation results show that the iron and manganese in sample G# are Fe 2+ and Mn 2+ , while the carbon content of the material of the test sample G# was 4.2wt%;

[0133] 5) Sample G# was used as the active material; the charge was then cut off after being charged to 4.5V. The positive electrode was disassembled from the battery in a glove box, cleaned with DMC for 3-5 times, evaporated to dryness in the glove box, and part of the electrode was taken for ICP (main detection elements: Na / Fe / Mn / Zn / Zr / P) test. The ICP test results showed that the element ratios of Na:Fe:Mn:Zn:Zr:P were 0.9:1.45:1.45:0.0498:0.0501:3.998, that is, when charged to 4.5V, there were 3 reversible sodium ions in the structure for deintercalation. At the same time, XPS test was performed on the iron and manganese elements in the above-mentioned electrode. The peak separation results showed that the iron and manganese in the above-mentioned electrode were Fe:Mn:Zn:Zr:P, respectively. 3+ and Mn 3+ , that is, only Fe 2+ / 3+ and Mn 2+ / 3+ Redox reaction between

[0134] 6) The electrode piece after disassembly and cleaning in step 6) was subjected to ICP test. The test results showed that the element ratio between Na:Li:Fe:Mn:Zn:Zr:P was 0.7:0.1:1.45:1.45:0.0498:0.0499:3.992. At the same time, XPS test was performed on the iron and manganese elements in the above electrode piece. The peak separation results showed that the iron and manganese in the above electrode piece were Fe 3+ and Mn 3+ , that is, Fe 2+ / 3+ and Mn 2+ / 3+ / 4+ Redox reaction between

[0135] 7) Take the battery after the discharge in step 7), disassemble the positive electrode from the battery in a glove box, wash it with DMC for 3-5 times, evaporate it in the glove box, and perform ICP test results. The element ratio between Na:Li:Fe:Mn:Zn:Zr:P is 3.7:0.2:1.45:1.45:0.0499:0.0499:4.01. At the same time, XPS is tested. The peak separation results show that the iron and manganese in the above-mentioned electrode are Fe 2+ and Mn 2+The electrode in the battery charged to 4.5V was washed with DMC for 3-5 times, evaporated in the glove box and then tested by XPS and ICP. The XPS test results showed that the prepared electrode material contained Fe 3+ and Mn 4+ , ICP test results show that the element ratio between Na:Li:Fe:Mn:Zn:Zr:P is 0.68:0.2:1.45:1.45:0.05:0.05:4;

[0136] Comparative Example 8-Na 3.8 Li 0.1 Fe2Mn 0.9 Zn 2+ 0.05 Zr 4+ 0.05 (PO4)2P2O7@C

[0137] The process and conditions are the same as those of Comparative Example 1, except that:

[0138] 1) Add 350 mL of deionized water to a beaker, and then add 0.2125 mol of citric acid monohydrate, C6H 10 O8, 3.7g starch, 0.2mol iron nitrate nine hydrate Fe(NO3)3.9H2O, 0.09mol manganese nitrate Mn(NO3)2 aqueous solution (50wt%), 0.005mol zinc acetate dihydrate Zn(Ac)2.2H2O, 0.005mol zirconium nitrate Zr(NO3) 4, The above raw materials are stirred until fully dissolved;

[0139] 4) Refined-XRD and ICP (main detection elements: Na / Fe / Mn / Zn / Zr / P) tests were performed on the heat-treated product. The element ratio of Na:Fe:Mn:Zn:Zr:P in ICP test was 3.9:2:0.9:0.05:0.05:3.99, which is Na 3.9 Fe2Mn 0.9 Zn 2+ 0.05 Zr 4+ 0.05 The (PO4)2P2O7@C material is consistent with the XRD refined structure and is recorded as sample H#. XPS test is performed on the iron and manganese in sample H#. The peak separation results show that the iron and manganese in sample H# are Fe 2+ and Mn 2+ , while the carbon content of the material of the test sample H# is 5wt%;

[0140] 5) Sample H# was used as the active material; the charge was then cut off after being charged to 4.5V. The positive electrode was disassembled from the battery in a glove box, cleaned with DMC for 3-5 times, evaporated to dryness in the glove box, and part of the electrode was taken for ICP (main detection elements: Na / Fe / Mn / Zn / Zr / P) test. The ICP test results showed that the element ratios of Na:Fe:Mn:Zn:Zr:P were 0.9:2:0.9:0.0498:0.0501:3.998, that is, when charged to 4.5V, there were 3 reversible sodium ions in the structure for deintercalation. At the same time, XPS test was performed on the iron and manganese elements in the above-mentioned electrode. The peak separation results showed that the iron and manganese in the above-mentioned electrode were Fe: 3+ and Mn 3+ , that is, only Fe 2+ / 3+ and Mn 2+ / 3+ Redox reaction between

[0141] 6) The electrode piece after disassembly and cleaning in step 6) was subjected to ICP test. The test results showed that the element ratio between Na:Li:Fe:Mn:Zn:Zr:P was 0.8:0.1:2:0.9:0.0499:0.05:3.997. At the same time, XPS test was performed on the iron and manganese elements in the above electrode piece. The peak separation results showed that the iron and manganese in the above electrode piece were Fe 3+ and Mn 3+ , that is, Fe 2+ / 3+ and Mn 2 + / 3+ / 4+ Redox reaction between

[0142] 7) Take the battery after the discharge in step 7), disassemble the positive electrode from the battery in a glove box, wash it with DMC for 3-5 times, evaporate it in the glove box, and perform ICP test results. The element ratio between Na:Li:Fe:Mn:Zn:Zr:P is 3.8:0.1:2:0.9:0.05:0.05:4.01. At the same time, XPS is tested. The peak separation results show that the iron and manganese in the above-mentioned electrode are Fe 2+ and Mn 2+ The electrode in the battery charged to 4.5V was washed with DMC for 3-5 times, evaporated in the glove box and then tested by XPS and ICP. The XPS test results showed that the prepared electrode material contained Fe 3+ and Mn 4+ , ICP test results show that the element ratio between Na:Li:Fe:Mn:Zn:Zr:P is 0.72:0.1:2:0.9:0.05:0.05:4;

[0143]

[0144]

[0145] in conclusion

[0146] The present invention provides a phosphate, pyrophosphate or phosphate-pyrophosphate composite polyanion compound with a new structure and a preparation method thereof. By precisely controlling the unit cell structure and the composite ratio between iron and manganese, the ionic conductivity and electronic conductivity of the compound are improved, the phase change behavior during the charge and discharge process can be effectively controlled, the reversibility of the electrochemical behavior can be improved, and the reaction kinetics can be improved, thereby improving the gram capacity, rate performance and cycle stability of the material. The prepared Na 3.8 Li 0.1 Fe 1.25 Mn 1.65 Zn 2+ 0.05 Zr 4+ 0.05 (PO4)2P2O7@C, the discharge capacity can reach 135mAh / g at 0.2C, the median voltage is as high as 3.69V, the discharge capacity can reach 115mAh / g at 1.0C, and the capacity retention rate is as high as 93% after 200 cycles under 1C / 1C charge and discharge conditions.

[0147] The composite ratio of iron and manganese affects the type of electrochemical behavior (such as solid solution and phase change) during the charge and discharge process of the material. When iron and manganese coexist, the reaction mechanism of solid solution and phase change coexistence is followed during the charge and discharge process of the material. When iron undergoes electrochemical oxidation-reduction behavior, the material presents a solid solution reaction mechanism, and when manganese undergoes electrochemical oxidation-reduction behavior, the material presents a phase change reaction mechanism. Different iron-manganese composite ratios affect the reversibility of the electrochemical behavior of the above two reaction mechanisms, thereby affecting the rate performance of the material and the capacity retention rate under cycle conditions. It is found through the embodiments and comparative examples of the present invention that when Na 3.8 Li 0.1 Fe 1.25 Mn 1.65 Zn 2+ 0.05 Zr 4+ 0.05 When the y value in the (PO4)2P2O7@C structure satisfies 3>y1>1.5, the prepared material has excellent rate performance and capacity retention rate, the discharge capacity at 0.2C can reach 125-135mAh / g, the median voltage is as high as 3.3V-3.69V, the discharge capacity at 1.0C can reach 93-115mAh / g, and the capacity retention rate after 200 cycles under 1C / 1C charge and discharge conditions is as high as 88%-94%. (such as: Examples 1, 8-9, Comparative Examples 7-8)

[0148] In order to alleviate the problem of unit cell volume shrinkage caused by the difference in ionic radius between high-valent manganese ions and divalent manganese ions, a small amount of B source ions are introduced into the unit cell structure (when the compound is as described in Formula I-1 or I-2, Formula II-1 or II-2, the range of z is 0.005≤z<0.2, preferably 0.05≤z≤0.1; when the compound is as described in Formula III-1 or III-2, Formula IV-1 or IV-2, the range of z is 0.005≤z≤0.05, preferably 0.01≤z≤0.02;), the B source ions and Mn 2+ Metal ions with similar ionic radii can effectively alleviate the above-mentioned volume change, improve the reversibility of the material during charge and discharge, reduce the polarization of the charge and discharge process, and improve the rate performance of the material. The appropriate amount of B source ion addition will also affect the above-mentioned effects. When the addition amount is too low, the improvement effect is not significant, and when the addition amount is too high, it will affect the number of active transition metal redox sites in the unit cell structure, thereby affecting the material's gram capacity. For example: Zn in Example 1-3 2+ ions, when 0.005≤z<0.2, the gram capacity of discharge at 0.2C can reach 120-135mAh / g, the median voltage is as high as 3.65V-3.69V, the gram capacity of discharge at 1.0C can reach 105-115mAh / g, and the capacity retention rate of 200 cycles under 1C / 1C charge and discharge conditions is as high as 91.5%-93%. Embodiment 1 is further preferred. When the above conditions are not met, the gram capacity and the discharge median voltage are reduced to a certain extent (such as: Comparative Examples 1-2); The JT effect of manganese in the unit cell structure will cause instability in the manganese cycle process, thereby affecting the cycle life. By adding an appropriate amount of B source ions in the structure, it can also stabilize the manganese position and further improve the cycle stability. For example, in Examples 1 and 3-4, the retention rate after 200 cycles at 1.0C / 1.0C can be as high as 87%-93%, while in Comparative Examples 3-4, the performance is reduced due to inappropriate addition or the effect of stabilizing manganese is not significant or too much addition affects the number of active sites.

[0149] Manganese ions exist Mn 2+ / Mn 3+ (3.6-3.8V vs Na+ / Na) and Mn 3+ / Mn 4+ (4.1-4.3V vs Na+ / Na) valence reaction process, that is, >1e- / Mn 2+ The electron transfer process can improve the material's gram capacity, but due to differences in the chemical environment, there are often some sodium ions in the structure that cannot achieve a reversible deintercalation process, and it is impossible to achieve 1e- / Mn 2+The electrochemical reaction provides available sodium ions. The presence of inert sodium ions leads to a low gram capacity of the material. At the same time, a small amount of lithium ions and magnesium ions are doped at the sodium site to stimulate the electrochemical activity of the inert sodium ions, thereby increasing the gram capacity of the material. The above dual effects have enabled the development of high-energy iron-manganese polyanion positive electrode materials.

[0150] The site doping of lithium ions and magnesium ions was directionally exchanged and rearranged by electrochemical ion exchange method, and the electrode material prepared above was charged to 4.5V vs Na in the battery. + / Na cutoff, XPS test results show that only Fe 2+ / 3+ and Mn 2+ / 3+ The disassembled electrode sheets are assembled into half-cells with metallic lithium in an electrolyte containing lithium salts and are charged in a specific voltage range (4.3V-4.6V vs Li + / Li) is charged and discharged. There is basically no first-cycle charge capacity in this process, that is, the inert sodium ions in the structure cannot be deintercalated, but there is a discharge capacity, that is, a certain amount of lithium ions are embedded in the structure, and within this voltage range, Li + The structure is continuously inserted and rearranged to reach a stable state, and the charge is (4.6V vs Li + / Li) after disassembling the electrode piece, the ICP test showed that the amount of lithium ions embedded in the structure was basically 0.1. After assembling the battery with sodium metal again, the discharge capacity was significantly improved. When the above battery was charged again to (4.5Vvs Na + / Na), the ICP test results show that in the subsequent charge and discharge process, Li does not participate in the redox reaction, and remains basically unchanged at 0.1, and the number of remaining sodium ions in the unit cell structure is reduced compared with the initial state, that is, the active "sodium ion increase" that can undergo reversible deintercalation, and XPS shows that when charged again to (4.5V vs Na + / Na), Fe 2+ / 3+ and Mn 2+ / 3+ / 4+ The redox reaction between the electrodes is carried out, and the gram capacity is significantly improved. The ion concentration in the electrolyte in the electrochemical ion exchange reaction involved in the process will also significantly affect the effect of the above process (such as: Examples 6-7). When the lithium salt concentration in the electrolyte is 0.05mol / L~0.3mol / L, 0.1 amount of Li can be effectively embedded in the positive electrode material. When the concentration is too low, the lithium ion mobility is too low and the above embedding effect cannot be achieved. When the concentration is too high, too much embedding will also cause disorder of the unit cell structure, causing performance degradation (such as: Comparative Examples 5-6); when Mg is used 0.05 The above-mentioned effects can also be achieved (such as: Example 10);

[0151] Similarly, the above rules also apply to electrode materials of other structures involved in the present invention, such as: Na 2.9-x Li a Fe 2-y-z Mn y B z (PO4)P2O7@C、Na 2.9-x Mg b Fe 2-y-z Mn y B z (PO4)P2O7@C、Na 1-x Li a Fe 1-y-z Mn y B z PO4@C、Na 1-x Mg b Fe 1-y-z Mn y B z PO4@C、Na 2-x Li a Fe 1-y-z Mn y B z P2O7@C、Na 2-x Mg b Fe 1-y-z Mn y B z P2O7@C can be used to prepare materials with excellent rate performance and cycle performance.

Claims

1. An iron-manganese polyanionic compound, characterized in that: The phosphate, pyrophosphate or phosphopyrophosphate composite polyanionic compound has one or more than two of the structures shown in Formula I-1 or Formula I-2 or Formula II-1 or Formula II-2 or Formula III-1 or Formula III-2 or Formula IV-1 or Formula IV-2: Na 3.9-x Li a Fe 3-y-z Mn y B z (PO4)2P2O7@C Formula I-1 Na 3.9-x Mg b Fe 3-y-z Mn y B z (PO4)2P2O7@C Formula I-2 Na 2.9-x Li a Fe 2-y-z Mn y B z (PO4)P2O7@C Formula II-1 Na 2.9-x Mg b Fe 2-y-z Mn y B z (PO4)P2O7@C Formula II-2 Na 1-x Li a Fe 1-y-z Mn y B z PO4@C Formula III-1 Na 1-x Mg b Fe 1-y-z Mn y B z PO4@C Formula III-2 Na 2-x Li a Fe 1-y-z Mn y B z P2O7@C Formula IV-1 Na 2-x Mg b Fe 1-y-z Mn y B z P2O7@C Formula IV-1 1) The phosphate, pyrophosphate or phosphate-pyrophosphate composite polyanion compound, wherein Fe and Mn in the structure are both Fe 2+ , Mn 2+ ; 0.01≤a≤0.15, more preferably 0.07≤a≤0.12, 0.005≤b≤0.075, more preferably 0.03≤b≤0.06 When having the structure shown in Formula I-1 or I-2: 2.995 > y > 1.5, more preferably 2.6 ≥ y ≥ 1.7; When having the structure shown in Formula II-1 or II-2: 1.995 > y > 1, more preferably 1.8 ≥ y ≥ 1.35; When having the structure shown in Formula III-1 or III-2 or Formula IV-1 or IV-2: 0.995 > y > 0.5, more preferably 0.85 ≥ y ≥ 0.6; 2) When the compound is as described in Formula I-1 or I-2, Formula II-1 or II-2, the range of z is 0.005 ≤ z ≤ 0.2, preferably 0.05 ≤ z ≤ 0.1; When the compound is as described in Formula III-1 or III-2, Formula IV-1 or IV-2, the range of z is 0.005 ≤ z ≤ 0.05, preferably 0.01 ≤ z ≤ 0.02; 3) In formula I-1 or I-2, formula II-1 or II-2, formula III-1 or III-2, formula IV-1 or IV-2, B is selected from Co 2+ 、Ni 2+ , Cu 2+ 、Zn 2 + 、Zr 4+ , Nb 3+ / 4+ 、Mo 3+ 、In 3+ Sn 4+ , Sb 3+ 、Ce 4+ 、 3+ / 4+ , W 4+ 、Bi 5+ , B 3+ One or more of the following, preferably Cu 2+ 、Zn 2+ 、Zr 4+ 、Mo 3+ 、In 3+ Sn 4+ 、 3+ / 4+ , W 4+ 、Bi 5+ , B 3+ One or more of the following; 4) The value of x should ensure that the electrode materials involved in Formula I-1 or I-2, Formula II-1 or II-2, Formula III-1 or III-2, Formula IV-1 or IV-2 are electrically neutral; When B is selected from Formula I-1, Formula II-1, Formula III-1, Formula IV-1: When B is selected from Co 2+ 、Ni 2+ , Cu 2+ 、Zn 2+ When one or more of the following are present, x=a; When B is selected from Nb 3+ 、Mo 3+ 、In 3+ , Sb 3+ 、 3+ , B 3+ One or more of the following, x=(a+z); When B is selected from Zr 4+ , Nb 4+ Sn 4+ 、Ce 4+ 、 4+ , W 4+ One or more of the following, x=(a+2z); When B is selected from Bi 5+ , x=(a+3z); When B is selected from Formula I-2, Formula II-2, Formula III-2, Formula IV-2: When B is selected from Co 2+ 、Ni 2+ , Cu 2+ 、Zn 2+ When one or more of the above are present, x=2*b; When B is selected from Nb 3+ 、Mo 3+ 、In 3+ , Sb 3+ 、 3+ , B 3+ One or more of the following, x=(2*b+z); When B is selected from Zr 4+ , Nb 4+ Sn 4+ 、Ce 4+ 、 4+ , W 4+ One or more of the following, x=(2*b+2z); When B is selected from Bi 5+ , x=(2*b+3z).

2. The compound according to claim 1, wherein it is a C-supported compound, where the mass content of C is 1 wt% - 10 wt%, more preferably 3 wt% - 6 wt%.

3. A method for preparing the compound according to claim 1 or 2, wherein the preparation process of the polyanionic compound shown in Formula I-1 or I-2, Formula II-1 or II-2, Formula III-1 or III-2, Formula IV-1 or IV-2 comprises the following steps: Step 1), using one or several of solid-phase calcination method, sol-gel method, solvothermal method, mix a sodium source, a phosphorus source, an iron source, a manganese source, a B source, and a carbon source to obtain a solid substance; The mixing method is one or more than two of ball milling, pot milling, sand milling, water dissolution, mechanical stirring, melting, etc.; Step 2), perform heat treatment on the solid substance obtained in Step 1); the solid substance must be in a powder state after being treated by methods such as crushing, ball milling, pot milling, etc. before heat treatment; The heat treatment includes a process of treating at a first temperature T1 and a process of treating at a second temperature T2 in sequence; the temperature T1 is 300 ≤ T1 ≤ 400 °C, and the treatment time is 0.5 - 8 h; The temperature T2 is 500 °C < T1 ≤ 800 °C, more preferably 600 °C < T1 ≤ 750 °C, and the treatment time is 3 - 20 h; The heat treatment is carried out in a specific flowing atmosphere, and the specific atmosphere is selected from at least one or more than two of inert atmospheres including argon, helium, nitrogen, or an inert atmosphere gas containing H2 with a volume concentration greater than 0 to less than 50%; Step 3) a, the heat-treated solid material obtained in step 2) is used as the positive electrode material active material to form a positive electrode plate, and the positive electrode plate is formed into a half-cell with the metal sodium negative electrode, and the active material and the metal sodium negative electrode are separated by a diaphragm. After the assembly is completed, the battery case is encapsulated and the voltage is 1.5V-4.5V vs Na + / Na voltage range, the charge and discharge cycles were performed 5-15 times, the electrolyte was (0.7-1.5) mol / L NaClO4 / EC (ethylene carbonate) / DEC (diethyl carbonate) (V / V = (0.2-0.5) / (0.5-0.8)) / (0.5-5) wt% FEC (fluoroethylene carbonate), and then charged to 4.5 V vs Na + / Na, the positive electrode sheet is disassembled from the battery in a glove box, washed with DMC (dimethyl carbonate) 3 to 5 times, and then evaporated to dryness in the glove box to obtain an evaporated electrode; Step 3)b, When the phosphate, pyrophosphate or phosphate-pyrophosphate composite polyanion positive electrode material is as shown in I-1, formula II-1, formula III-1, and formula IV-1, the evaporated electrode is reassembled into a half-cell with a metal lithium negative electrode, and the active substance and the metal lithium negative electrode are separated by a diaphragm. After the assembly is completed and the battery shell is packaged, the electrolyte is selected from (0.05-0.3) mol / L LiPF6+(0.35-1.45) mol / LNaClO4 / EC / DEC (V / V=(0.2-0.5) / (0.5-0.8)) / (0.5-5) wt% FEC, and more preferably (0.1-0.2) mol / L LiPF6+(0.8-0.9) mol / L NaClO4 / EC (ethylene carbonate) / DEC (diethyl carbonate) (V / V = (0.2-0.5) / (0.5-0.8)) / (0.5-5) wt% FEC (fluoroethylene carbonate), at 4.3V-4.6V vs Li + / Li voltage range for 5-15 charge and discharge cycles, preferably 8-10 times, and then charged to 4.5V-4.6Vvs Li + / Li is cut off and charged to 4.5V-4.6Vvs Li in the glove box + The positive electrode sheet in the battery that was cut off after / Li was disassembled from the battery, washed with DMC (dimethyl carbonate) 3-5 times, and then evaporated to dryness in a glove box; The disassembled and cleaned evaporated electrode is again assembled into a half-cell with a metal sodium negative electrode in a glove box, the active material is separated from the metal sodium negative electrode by a diaphragm, and the battery shell is packaged after assembly. The electrolyte is (0.7-1.5) mol / L NaClO4 / EC (ethylene carbonate) / DEC (diethyl carbonate) (V / V = (0.2-0.5) / (0.5-0.8)) / (0.5-5) wt% FEC (fluoroethylene carbonate), and the diaphragm is a glass fiber membrane. The charge and discharge cycle is performed 5-10 times in the voltage range of 1.5V-4.5V; the battery after discharge is taken, the positive electrode plate is disassembled from the battery in the glove box, and DMC (dimethyl carbonate) is used for washing 3-5 times, and then evaporated in the glove box; The active substance in the phosphate, pyrophosphate or phosphate-pyrophosphate composite polyanion positive electrode plate obtained by the disassembly is the phosphate, pyrophosphate or phosphate-pyrophosphate composite polyanion compound described in I-1, formula II-1, formula III-1, and formula IV-1; Or, when the phosphate, pyrophosphate or phosphate-pyrophosphate composite polyanion positive electrode material is as shown in I-2, II-2, III-2, IV-2, the evaporated electrode is reassembled into a half-cell with a metal Mg negative electrode, and the electrolyte is selected from (0.1-0.4) mol / L Mg(TFSI)2+(0.3-1.4) mol / L NaClO4 / EC(ethylene carbonate) / DEC(diethyl carbonate) (V / V=(0.2-0.5) / (0.5-0.8)) / (0.5-5) wt% FEC(fluoroethylene carbonate) or (0.15-0.5) mol / L Mg(TFSA)2+(0.3-0.1.35) mol / L NaClO4 / EC (ethylene carbonate) / DEC (diethyl carbonate) (V / V = (0.2-0.5) / (0.5-0.8)) / (0.5-5) wt% FEC (fluoroethylene carbonate), more preferably (0.2-0.3) mol / L Mg(TFSI)2 or Mg(TFSA)2 + (0.3-1.4) mol / L NaClO4 / EC (ethylene carbonate) / DEC (diethyl carbonate) (V / V = (0.2-0.5) / (0.3-1.4)) / (0.5-5) wt% FEC (fluoroethylene carbonate), at 4.0V-4.2V vs Mg 2+ / Mg voltage range for 5-15 charge and discharge cycles, preferably 8-10 times, and then charged to 4.1V-4.2Vvs Mg 2+ / Mg is cut off and charged to 4.1V-4.2Vvs Mg in the glove box 2+ The phosphate, pyrophosphate or phosphate-pyrophosphate composite polyanion positive electrode sheet in the battery cut off after / Mg is disassembled from the battery, washed with DMC (dimethyl carbonate) 3 to 5 times, and then evaporated to dryness in a glove box; The active substances in the phosphate, pyrophosphate or phosphate-pyrophosphate composite polyanion positive electrode plates obtained by disassembly are the phosphate, pyrophosphate or phosphate-pyrophosphate composite polyanion compounds described in I-2, II-2, III-2 and IV-2.

4. The method for preparing the compound according to claim 3, characterized in that: The solid phase calcination method described in step 1) comprises the following process: The sodium source, phosphorus source, iron source, manganese source, B source and carbon source are uniformly mixed to obtain a solid precursor; When insoluble raw materials exist in the sodium source, phosphorus source, iron source, manganese source, B source and carbon source, the mixing method is ball milling, jar milling and sand milling, and a solvent needs to be added during mixing to obtain a precursor slurry, the solvent is water, ethanol, or a mixed solvent of water and ethanol, the mass of water in the mixed solvent preferably accounts for (30-80) wt%, more preferably (45-55) wt%, the mass of ethanol accounts for (20-70) wt%, more preferably (45-55) wt%, when the particle size range of the precursor slurry is 0.5 μm-1.0 μm, the precursor slurry is pumped into the atomizer of the spray dryer by a peristaltic pump, and the powder is collected; after the precursor slurry is dried, a solid precursor with a particle size of 20 μm-30 μm is obtained; When there is no insoluble raw material in the sodium source, phosphorus source, iron source, manganese source, B source, and carbon source, and the mixing method is dissolution, a solvent needs to be added to the mixture to obtain a precursor solution, and the solvent is water. The precursor solution is pumped into the atomizer of the spray dryer through a peristaltic pump to collect powder; after the precursor slurry is dried, a solid precursor with a particle size of 20μm-30μm is obtained; When the sodium source, phosphorus source, iron source, manganese source, B source and carbon source are mixed in a melting manner, the raw materials are placed in a graphite crucible, and the temperature is rapidly raised to a temperature at which the raw materials are in a fluid state, and the temperature is maintained for 0.5 hours, and then rapidly cooled to room temperature within 2-5 minutes to obtain a molten raw material; the molten raw material is ball-milled to obtain a solid precursor, and the particle size of the solid precursor is 25 μm-35 μm; the ball milling speed is 300 r / min-800 r / min, and more preferably 400 r / min-500 r / min; the ball milling time is 2h-8h, and more preferably 3.5h-5h; The spray drying described in step 1 is preferably controlled to control the feed flow rate to 20mL / min~60mL / min, the inlet air temperature to 120℃~195℃, the exhaust port temperature to 80℃~110℃, the compressed air pressure to 0.03KPa~0.9KPa, and the precursor slurry is pumped into the spray dryer atomizer through a peristaltic pump to collect the powder; after the precursor slurry is dried, a precursor powder with a particle size of 20μm-30μm is obtained. Or, the sol-gel method described in step 1) includes the following process: When there is no insoluble raw material in the sodium source, phosphorus source, iron source, manganese source, B source and carbon source, and the mixing method is water dissolution, a solvent needs to be added to the mixture to obtain a precursor solution, and the solvent is water. The precursor solution is heated in a water bath to evaporate the water in the precursor solution until it is in a gel state and then transferred to a blast drying oven for drying; the water bath heating temperature is 65°C-95°C, more preferably 80°C-90°C; the drying temperature is 70°C-120°C, more preferably 85°C-100°C; the solid obtained after drying is ground or ball-milled into a powder state to obtain a solid precursor with a particle size of 25μm-35μm; the ball milling speed is 300r / min-800r / min, more preferably 400r / min-500r / min; the ball milling time is 2h-8h, more preferably 3.5h-5h; Or, the solvothermal method described in step 1) comprises the following steps: a. Transferring the sodium source, phosphorus source, iron source, manganese source, B source and carbon source into a polytetrafluoroethylene liner in a reaction kettle, and adding a solvent during mixing to obtain a precursor reaction liquid, wherein the solvent is water, ethanol, or a mixed solvent of water and ethanol, wherein the mass of water in the mixed solvent preferably accounts for (30-80) wt%, more preferably (45-55) wt%, and the mass of ethanol preferably accounts for (20-70) wt%, more preferably (45-55) wt%; b. Transfer the precursor reaction liquid to a forced air drying oven at a temperature of 120°C-200°C, more preferably 150°C-180°C; set the time to 8h-20h, more preferably 8h-12h; after the above process is completed, take out the reactor, pour out the upper reaction liquid, transfer the solid precipitate at the bottom of the reactor to a centrifuge tube, wash it with deionized water and ethanol three to five times respectively, collect the precipitated material after washing, transfer it to a forced air drying oven at a temperature of 80°C-120°C, more preferably 95°C-105°C, and obtain the solid precursor after drying.

5. The method for preparing the compound according to claim 3 or 4, characterized in that: Preferably, the phosphate polyanionic compound is a structure of formula I-1, and the molar ratio of the sodium source, lithium source, iron source, manganese source, B source, and phosphorus source is (3.9-x):a:(3-yz):y:z:(3.95-4.05), and the molar ratio of the sodium source, iron source, manganese source, B source, and phosphorus source is based on the molar amount of sodium, lithium, iron, manganese, B, and phosphorus, respectively; Preferably, the phosphate polyanionic compound is a structure of I-2 as shown in formula, the molar ratio of the sodium source, magnesium source, iron source, manganese source, B source, and phosphorus source is (3.9-x):b:(3-yz):y:z:(3.95-4.05), and the molar ratio of the sodium source, iron source, manganese source, B source, and phosphorus source is based on the molar amount of sodium, magnesium, iron, manganese, B, and phosphorus, respectively; Preferably, the phosphate polyanionic compound is a structure of II-1 as shown in formula, the molar ratio of the sodium source, lithium source, iron source, manganese source, B source, and phosphorus source is (2.9-x):a:(2-yz):y:z:(2.95-3.05), and the molar ratio of the sodium source, lithium source, iron source, manganese source, B source, and phosphorus source is based on the molar amount of sodium, lithium, iron, manganese, B, and phosphorus, respectively; Preferably, the phosphate polyanionic compound is a structure of II-2 as shown in formula, the molar ratio of the sodium source, magnesium source, iron source, manganese source, B source, and phosphorus source is (2.9-x):b:(2-yz):y:z:(2.95-3.05), and the molar ratio of the sodium source, magnesium source, iron source, manganese source, B source, and phosphorus source is based on the molar amount of sodium, magnesium, iron, manganese, B, and phosphorus, respectively; Preferably, the phosphate polyanionic compound is a structure of III-1 as shown in formula, the molar ratio of the sodium source, lithium source, iron source, manganese source, B source, and phosphorus source is (1-x):a:(1-yz):y:z:(0.95-1.05), and the molar ratio of the sodium source, lithium source, iron source, manganese source, B source, and phosphorus source is based on the molar amount of sodium, lithium, iron, manganese, B, and phosphorus, respectively; Preferably, the phosphate polyanionic compound is a structure of III-2 as shown in formula, the molar ratio of the sodium source, magnesium source, iron source, manganese source, B source, and phosphorus source is (1-x):b:(1-yz):y:z:(0.95-1.05), and the molar ratio of the sodium source, magnesium source, iron source, manganese source, B source, and phosphorus source is based on the molar amount of sodium, magnesium, iron, manganese, B, and phosphorus, respectively; Preferably, the phosphate polyanionic compound is a structure of IV-1 as shown in formula, the molar ratio of the sodium source, lithium source, iron source, manganese source, B source, and phosphorus source is (2-x):a:(1-yz):y:z:(1.95-2.05), and the molar ratio of the sodium source, lithium source, iron source, manganese source, B source, and phosphorus source is based on the molar amount of sodium, lithium, iron, manganese, B, and phosphorus, respectively; Preferably, the phosphate polyanionic compound has the structure of IV-2 as shown in formula, and the molar ratio of the sodium source, magnesium source, iron source, manganese source, B source and phosphorus source is (2-x):b:(1-yz):y:z:(1.95~2.05), and the molar ratio of the sodium source, magnesium source, iron source, manganese source, B source and phosphorus source is calculated based on the molar amount of sodium, magnesium, iron, manganese, B and phosphorus, respectively.

6. The method for preparing the compound according to claim 3 or 4, characterized in that: The sodium source is selected from at least one or more of sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium acetate, sodium citrate, sodium oxalate, sodium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, sodium pyrophosphate, and sodium hydrogen pyrophosphate; The iron source is selected from one or more of iron powder, ferroferric oxide, ferrous oxide, ferric oxalate, ferrous oxalate (dihydrate), ferric phosphate, ferric pyrophosphate, ferrous citrate, ferric nitrate, ferrous nitrate, ferrous sulfate, ferrous sulfate, ferrous chloride, ferrous chloride, ferrous acetate, ammonium ferrous sulfate, ferric citrate, ammonium ferric citrate, and sodium ferric citrate succinate; The manganese source is selected from one or more of manganese monoxide, manganese dioxide, manganese trioxide, manganese tetraoxide, manganese hydroxide, manganese sulfate, manganese chloride, manganese nitrate, manganese phosphate, manganous phosphate, manganese dihydrogen phosphate, and manganese nitrate tetrahydrate; The phosphorus source is selected from at least one or more of diammonium dihydrogen phosphate, diammonium hydrogen phosphate, phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate, pyrophosphoric acid, sodium pyrophosphate, and sodium hydrogen pyrophosphate; The B source is selected from one or more of oxides, hydroxides, carbonates, sulfates, chlorides, sulfates, phosphates, etc. corresponding to the metal ions; The carbon source is selected from at least one or more of starch, carboxymethyl starch, sodium carboxymethyl starch, sodium alginate, citric acid, oxalic acid, ammonium citrate, ascorbic acid, formaldehyde, acetaldehyde, lactic acid, malic acid, glucose, sucrose, maltose, and maltodextrin.

7. The method for preparing the compound according to claim 3 or 4, characterized in that: The preparation process of the positive electrode sheet is as follows: the positive electrode material active substance is mixed with the conductive agent and the binder, and an organic solvent is added to form a paste after mixing evenly, and then the paste is coated on the aluminum current collector and dried to obtain the paste; In the positive electrode material, the content of the polyanionic compound electrode material is (60-98) wt%; The positive electrode material further contains a conductive agent and a binder, wherein the mass ratio of the iron-based phosphate or fluorophosphate polyanionic compound, the conductive agent and the binder is (60-98) wt%: (1-39) wt%: (1-39) wt%; The conductive agent is at least one or more of carbon black, conductive graphite, carbon fiber, carbon nanotube, and graphene; The binder is polyvinylidene fluoride: at least one or more of PVDF5130, HSV900 and kynar761A.

8. Use of the polyanionic compound according to claim 1 or 2 in a sodium ion battery, characterized in that: Phosphates, pyrophosphates or phosphate-pyrophosphate composite polyanionic compounds are used as active substances of electrode materials for sodium ion batteries.

9. The use according to claim 8, characterized in that: Polyanionic compounds are used as positive electrode active materials for sodium ion batteries.

10. The use according to claim 9, characterized in that: In the positive electrode material, the content of the polyanionic compound electrode material is (60-98) wt%; The positive electrode material further contains a conductive agent and a binder, wherein the mass ratio of the iron-based phosphate or fluorophosphate polyanionic compound, the conductive agent and the binder is (60-98) wt%: (1-39) wt%: (1-39) wt%; The conductive agent is at least one or more of carbon black, conductive graphite, carbon fiber, carbon nanotube, and graphene; The binder is polyvinylidene fluoride: at least one or more of PVDF5130, HSV900 and kynar761A.

Citation Information

Patent Citations

  • Positive electrode material for sodium batteries and method for producing same

    CN104364946A

  • Modified iron-based polyanionic compound positive electrode material and preparation method thereof

    CN113328073A

  • Preparation method and application of sodium-ion battery positive electrode material ferric sodium pyrophosphate

    CN114538403A

  • Sodium-ion battery positive electrode material prepared by gel method and preparation method of sodium-ion battery positive electrode material

    CN114873575A

  • Preparation method and application of pyrophosphoric acid ferric manganese phosphate sodium (at) C composite material

    CN115312734A